QCGN Pleased by Federal Support for Minority Economic-Development Plan - Quebec Community Groups Network (QCGN) (2024)

Adaptation Initiative Project Guide : 2023-2028 - Community Health and Social Services Network (CHSSN) (2024)
This guide to the CHSSN Adaptation Projects 2023– 2028 gives the descriptions of the projects being carried out by our public partners to improve access to health services across the province. These projects take into account the diverse regional realities of the English-speaking communities and are designed to have a direct impact on the ability of an Englishspeaking client to access services in English. Each region develops a project that will advance their capacities to understand the needs of the community and better respond to them. The primary objectives of this program are to 1) improve access to health and social services in English in all regions and 2) support better communication and partnerships between the English-speaking community and public health establishments.

Busting Myths : Report Shows English-speaking Quebecers Are Key Part of a National-Unity Solution - Quebec Community Groups Network (QCGN) (2024)

A Truly Brave Space : CHSSN's Provincial Mental Health & Wellness Forum - Community Health and Social Services Network (CHSSN) (2024)

CHSSN Annual Report : 2023-2024 - Community Health and Social Services Network (CHSSN) (2024)

English Speaking Catholic Council : 2023-2024 Annual Report - English Speaking Catholic Council (2024)

Youth Mental Health Initiatiive : Final Evaluation Report : 2021-2024 - Glass, Juniper (Community Health and Social Services Network (CHSSN), 2024)
The Youth Mental Health Initiative promotes the mental health of English-speaking youth by improving their access to resources and services and involving them in the design and implementation of activities that promote their agency and reduce stigma in their peers and community. In 2021-24, YMHI focused on mental health literacy and awareness building with youth while promoting the adaptation of mental health services and resources to be more inclusive, youth-friendly and culturally appropriate to reach underserved English-speaking youth.

Annual Report 2023-2024 - Provincial Employment Roundtable (PERT) (2024)

Pre-Budget Submission 2024-2025 - Provincial Employment Roundtable (PERT) (2024)
The Provincial Employment Roundtable Table (PERT) is pleased to submit this brief and proposition to the Ministry of Finance’s 2024-25 Pre-budget consultations. Founded in 2020, PERT is a non-profit organization focused on addressing the employment and employability issues that are being faced by Québec’s English-speaking communities. Since its creation, PERT has become the leading voice on the solutions to English speakers’ employment challenges. Through its research and stakeholder coordination work, PERT has published over 25 reports that capture the employment issues and needs of English speakers across all 17 regions of the province and has established a membership of 90 employment service deliverers, educational institutions, regional organizations, and employers. The employment situation of Québec’s English-speaking population continues to worsen, as demonstrated by the higher unemployment rates and French-language barriers that English speakers face in Québec’s labour market. In this brief, we identify two key contributors to the continued employment challenges of English speakers: a lack of targeted employment services and programs for English speakers and a lack of work-integrated French language training programs to help them enter and remain in the labour market. English speakers’ employment and economic challenges are part of the larger economic headwinds that are facing Québec, which include unprecedented labour shortages, demographic decline, and problems with attracting and retaining talent. This mémoire summarizes PERT’s research findings, particularly the employment challenges facing the English-speaking community in Québec, and advances recommendations for the next budget that will address these challenges and help create a more productive, inclusive, and prosperous Québec for all.

Annual Report : April 1, 2023 to March 31, 2024 - Quebec English-Speaking Communities Research Network (QUESCREN) (2024)

What Is a Home & School Association? And What Can It Do for Your School Community? - Quebec Federation of Home and School Associations (QFHSA) (2024)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by theSecrétariat aux relations avec les Québécois d’expression anglaise from December 2021to the present.
Keywords: Official Language Minority Community (OLMC)

Inclusive Mentorship Initiative - Townshippers' Association (2024)
This report provides an overview and evaluation of the 2023-2024 fiscal year ofTownshippers’ Association’s Inclusive Mentorship Initiative (IMI) funded by the Secrétariat aux relations avec les Québécois d’expression anglaise from December 2021 to the present. Founded in 1979, Townshippers’ Association is mandated to promote the interests ofthe ESC in the historical Eastern Townships, strengthening the cultural identity of thiscommunity, and encouraging the full participation of the English-speaking population in the community at large. Townshippers’ Association’s projects address heritage andculture, community development, access to health and social services, support for seniors, and youth retention. The Secretariat aux relations avec les Québécois d’expression anglaise is responsible forensuring that the concerns of English-speaking Quebecers are taken into account ingovernment orientations and decisions in collaboration with government ministries and bodies.

Townshippers' Association Annual Report 2023-2024 - Townshippers' Association (2024)

Searching for a Work-Life Balance in Your Health and Social Services Career? - Townshippers' Association; Dialogue McGill (2024)

Déclaration commune en réponse à un rapport publié par Mario Beaulieu, député / Joint Statement in Response to Report Released by Mario Beaulieu, M.P. - English Language Arts Network (ELAN); Quebec Writers' Federation (QWF); Quebec Drama Federation (QDF); Association of English-language Publishers of Quebec (AELAQ) (2023)
Keywords: Official Language Minority Community (OLMC)

Supporting the Economic Development of Québec’s English-Speaking Communities - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is pleased to submit this brief and present it to the Standing Committee on Official Languages to contribute to its study of the economic development of official language minority communities (OLMCs). We believe this is an important study, which we hope will shed light on the needs of our community and lead to the development of new government actions that address the economic development challenges in Québec’s English-speaking communities, particularly in employment and employability.
Keywords: Official Language Minority Community (OLMC)

Synergistic Expertise Supporting Pedagogical Development and Innovation - Cooperberg, Andrea; Argento, Amanda; Turgeon, Chantal; Regan, Susan; Hackett, Teresa; Brown, Douglas; Prévost, Nathalie; Crossland, Constance (QUESCREN Education and Vitality Forum 2023, 2023)

Fostering Intergenerational Connections and Experiential Learning Through Community Gardening - Zbarcea, Andreea; Di Bartolo Rouillier, Jessica (QUESCREN Education and Vitality Forum 2023, 2023)

Canada, Quebec, and Intergovernmental Agreements to Support English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

New CDA Orientation Guide - Leading English Education and Resource Network (LEARN) (2023)

August & September 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

June & July 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Powered with $1.1 Million of Funding, 10 Innovative CIF 2.0 Projects Benefit 1,500 Youth and Seniors Across English-speaking Quebec - Quebec Community Groups Network (QCGN) (2023)

[CEDEC Newsletter] - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

CEDEC hopeful Official Languages Act Action Plan will have long-term impact and meaningful difference to ESCQ vitality - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Newsletter - Seniors Action Quebec (2023)

Annual Report April 1, 2022 to March 31, 2023 - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

E-Magazine : Better Economies for Better Lives - Community Economic Development and Employability Corporation (CEDEC) (2023)

February & March 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2023)

Impact Report 2022-2023 - 4Korners (2023)

Black Academic Scholarship Fund 2023 Award Luncheon - Black Academic Scholarship Fund (BASF) (2023)

Committee for Anglophone Social Action Annual Report - Committee for Anglophone Social Action (CASA) (2023)

Annual Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)

Community Mobilization Model for Improving Health and Well-being of English-speaking Communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community Mobilization Model : For improving the health and well-being of English-speaking communities in Quebec - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)

Investing in the Vitality of English-speaking Quebec / Investir dans la vitalité du Québec d'expression anglaise - Community Health and Social Services Network (CHSSN) (2023)
Keywords: Official Language Minority Community (OLMC)

Networking and Partnership Initiative / Initiative de réseautage et de partenariat (NPI) - Community Health and Social Services Network (CHSSN) (2023)

Youth Mental Health Initiative : Impact Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Within the Youth Mental Health Initiative’s (YMHI) second year, CHSSN supported 27 community organizations with over 373 partnerships across 12 regions of Quebec including three provincial organizations, with the central goal of improving the access of mental health services and resources to Quebec’s English-speaking youth between the ages of 15-29. Each organization has worked to identify gaps in youth mental health services; engage youth in program design; partner with local schools, public health services and other community organizations; adapt, translate, and produce resources; and offer activities and programs for young people to help fill some of the gaps. Through a community of practice and individualized support, CHSSN helped community organizations to build their knowledge, network with each other and problem solve on program implementation.

Annual Report 2022-2023 - English Speaking Catholic Council (2023)

Learning Landscapes Journal : Education in a Pivotal Time : The Moment for Inspiration, Innovation, and Change - Leading English Education and Resource Network (LEARN) (2023)

2022-2023 Activity Report - Literacy Quebec (LQ) (2023)

Annual Report : 2022-2023 - Montérégie West Community Network (MWCN) (2023)

Annual Report : 2022-2023 - NDG Community Council (NDGCC) (2023)

Annual Report 2021-2022 - Provincial Employment Roundtable (PERT) (2023)

Annual Report 2022-2023 - Provincial Employment Roundtable (PERT) (2023)

Strategic Plan 2024-2027 : The Way Forward - Provincial Employment Roundtable (PERT) (2023)
The Provincial Employment Roundtable (PERT) is a non-profit multi-stakeholder initiative focused on addressing the employment and employability challenges facing Québec’s English-speaking community. This strategic plan for 2024-2027 outlines five key shifts, the introduction of a third organisational pillar, and eleven strategic goals that will guide PERT’s efforts to address the unique employment challenges faced by English speakers in Québec.

Fostering Great Working Relationships in Your School Community - Quebec Federation of Home and School Associations (QFHSA) (2023)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2023)

Annual Report 2022-2023 - Seniors Action Quebec (SAQ) (2023)

Townshippers' Association Annual Report 2022-2023 - Townshippers' Association (2023)

Annual Report - Vision Gaspé-Percé Now (2023)

Annual Report - Voice of English-speaking Quebec (VEQ) (2023)

The Yellow Door : 2022-2023 Annual Report / La Porte Jaune : 2022-2023 Rapport annuel - Yellow Door (2023)

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

Jamaica Association Election 2022 : Saturday, December 10, 2022 : 7pm About the Candidates - Jamaica Association of Montreal (JAM) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Newsletter : October - December 2022: Volume 26 - Jamaica Association of Montreal (JAM) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

December 2022 & January 2023 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

E-Magazine : A trusted leader of innovative collaboration among the public, private and civil society sectors - Community Economic Development and Employability Corporation (CEDEC) (2022)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

Community Learning Centres : Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2022)

November 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

What the Community School Approach Brings to Quebec's English School Sector: Connections, Connections, Connections - Horrocks, Debbie; Loomer, Benjamin; Lamarre, Patricia (Lunch & Learn, 2022)

October 2021 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Roles and Responsibilities : CLC Team Members, School Boards and LEARN's Provincial Resource Team - Leading English Education and Resource Network (LEARN) (2022)

September 2022 eBulletin - McGill Community For Lifelong Learning (MCLL) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

September 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Newsletter: August 2022 : Independence Special Edition : Volume 25.1 - Jamaica Association of Montreal (JAM) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

July 2022 : Newsletter - Coasters Association (2022)

July & August 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

41st Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2022)

Minutes of the Annual General Meeting of “Agape” Inc. - AGAPE (2022)

RAWQ Appoints Paul Tonkin as Executive Director - Ayers, Arthur (2022)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2022)

2021-2022 Annual Report : Saint Brigid's Home Residents' Committee - King, Kerry-Anne (Jeffery Hale - Saint Brigid's (JHSB), 2022)

Jamaica Association of Montreal Newsletter : Apr. - Jun. 2022 : Vol. 24 - Jamaica Association of Montreal (JAM) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Report on the Education and Vitality Forum : Overview - Macris, Antonia; QUESCREN (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Board of Directors : 2022-2024 - Coasters Association (2022)

AGM Minutes : March 22, 2022 - Griffin, Priscilla (Coasters Association, 2022)

QFHSA News Bulletin - Quebec Federation of Home and School Associations (QFHSA) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Activity Report : A Year In Review 2021-22 - Literacy Quebec (LQ) (2022)

Annual Report : April 1, 2021 to March 31, 2022 - Quebec English-speaking Communities Research Network (QUESCREN) (2022)

Coasters 27th General Meeting & 33rd Anniversary - Coasters Association (2022)

Coasters 27th General Meeting & 33rd Anniversary Program - Coasters Association (2022)

Our Local Pioneers! : A Podcast on the Collaboration between Francophones and Anglophones in the Outaouais and their Contributions to Quebec Society, from Yesterday to Today - Nivischiuk, Jeanne (2022)

Follow-up Report - Maurice, Cornella (Coasters Association, 2022)

Coasters Staff Contact List - Coasters Association (2022)

March 2022 : Newsletter - Coasters Association (2022)

Jamaica Association of Montreal Newsletter : Jan - Mar 2022 : Vol. 23 - Jamaica Association of Montreal (JAM) (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

March 2022 : Monteregie West Community Network - Montérégie West Community Network (MWCN) (2022)

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Strategic Restructuring Plan : The Road Ahead - Maurice, Cornella; Buffitt, Kimberly; Fequet, Roderick; Keats, Shannon; Griffin, Priscilla; Maynard, Hugh; Geukjian, Nadia (Coasters Association, 2022)

Operating Rules - McGill Community For Lifelong Learning (MCLL) (2022)

The Partnership Approach : Celebrating Resiliency Conference - Pocock, Joanne (2022)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Improving the Health and Well-being of English-speaking Seniors in the Laurentians, Québec : A Needs Assessment - Helou, Rola; Finch, Lois; Richardson, Mary (4Korners, 2022)
This needs assessment was commissioned by the 4Korners Laurentian Community Network, a registered Canadian charitable organization founded in 2005, which connects individuals of the Laurentians with programs and services to meet their needs in a secure and inclusive environment. The objective was to identify the needs of the aging English-speaking population in the Laurentians and to determine if they are currently being met. The First Nations Adult Education School Council conducted the assessment in partnership with S.O.A.R. Solutions, a consulting firm. The work was overseen by a committee (the Seniors’ Needs Assessment Committee, SNAC), made up of 4Korners employees, volunteers, the Elders’ Community Worker from the Kanesatake Health Center and project consultants from the First Nations Adult Education School Council.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Impact Report 2021-2022 - 4Korners (2022)

Annual Report 2021-22 - Committee for Anglophone Social Action (CASA) (2022)

Annual Report : 2021-2022 - Community Health and Social Services Network (CHSSN) (2022)

Outil de référence pour venir en aide aux enfants et aux familles d’expression anglaise vulnérables / Reference Tool for Reaching Vulnerable English-speaking Children and Families - Community Health and Social Services Network (CHSSN) (2022)

Working Together for a More Vital Community : The 2022-2027 Community Developmet Plan for English-speaking Quebec - Community Vitality Roundtables (Quebec Community Groups Network (QCGN), 2022)
The community sector serving English-speaking Quebec cultivates a sustained, ongoing capacity to collect, analyze, and share information (qualitative and quantitative) necessary to more deeply understand our community.

Arts-Based Performances, Perspectives, and Approaches in Research and Pedagogy - Leading English Education and Resource Network (LEARN) (2022)

Fall 2022 : MCLL News - McGill Community For Lifelong Learning (MCLL) (2022)

Impact Report : 2021-2022 - Megantic English-speaking Community Development Corporation (MCDC) (2022)

Annual Report 2021-2022 - Montérégie West Community Network (MWCN) (2022)

Society Pages - Morrin Centre (2022)

Society Pages - Morrin Centre (2022)

Annual Report : 2021-2022 - NDG Community Council (NDGCC) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

QFHSA News : The News Magazine for Home and School Members - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-01 : Objection to the Definition of “Historic” Anglophones and the Consequent Restrictions to Eligibility for Services in English - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-02 : Request to Maintain Race, Religion, and Culture as Central Themes in the Proposed Citizenship Course - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-03 : A Call to Suspend and Amend Law 21 - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-04 : Request to Be Included in Future Consultations as a Partner in Education - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-05 : The Offering of Bilingual Services by Student Ombudsmen - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-06 : Immigrating Ukrainian Children - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-07 : Quebec English CEGEP Curricula - Quebec Federation of Home and School Associations (QFHSA) (2022)

Resolution 2022-08 : Quebec English CEGEP Admissions Policy - Quebec Federation of Home and School Associations (QFHSA) (2022)

Annual Report - Réseau de l’est de l’île pour les services en anglais (REISA) (2022)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2022)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

2021-2022 : Annual Report / Rapport annuel - Seniors Action Quebec (SAQ) (2022)

2021-2022 Annual Report - The English Speaking Catholic Council (2022)

Townshippers' Association Annual Report 2021-2022 - Townshippers' Association (2022)

Annual Report - Vision Gaspé-Percé Now (2022)

The Yellow Door : 2021-2022 Annual Report / La Porte Jaune : 2021-2022 Rapport annuel - Yellow Door (2022)

Showing up when it counts : 2021 Annual report - Youth Employment Services (YES) (2022)

Jamaica Association of Montreal Newsletter : Oct. - Dec. 2021 : Vol. 22 - Jamaica Association of Montreal (JAM) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Community Development Plan 2022-2027 : Roundtable - Quebec Community Groups Network (QCGN) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

The Regional Association of West Quebecers Announces 2021-2022 Board of Directors - Ayers, Arthur (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Data Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Current Situation Report : Funding Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.
Keywords: Official Language Minority Community (OLMC)

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Organization and Network Health Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Community Development Plan for the English-speaking Community of Quebec 2022-2027 - Environmental Scan Report : Representation Roundtable - Quebec Community Groups Network (QCGN) (2021)
The Community Development Plan is a framework for collective action undertaken by the community sector of English-speaking Quebec to ensure its continued vitality. Through coordinated, strategic action, the community asserts collective control over resources allocated to it to ensure its development. The purpose of this report is to offer a portrait of the current situation of English-speaking Quebec’s Community sector with respect to the data development area. Together with similar reports in the other three areas, this provides a framework to help the Community Development Plan produce outcomes in line with our shared priorities.

Network News - Quebec Community Groups Network (QCGN) (2021)

2nd Annual General Meeting and "Moving Forward in Partnership" Presentations - Regional Development Network (RDN) (2021)

Jamaica Association of Montreal Newsletter : Jul. - Sept. 2021: Volume 21 : Summer 2021 Edition - Jamaica Association of Montreal (JAM) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

RAWQ Appoints Jeanne Nivischiuk as Exectuive Director - Regional Association of West Quebecers (RAWQ) (2021)

Directory of Services - Jamaica Association of Montreal (JAM) (2021)

RAWQ Statement on the Official Languages of Quebec and Canada - Regional Association of West Quebecers (RAWQ) (2021)

Resolution 2021-01 : Free French Instruction Services for all Who Request Them - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-02 : Evaluation Improvements, and Investments in School Buildings - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-04 : Request to Revise and Improve the Secondary III and Secondary IV History of Quebec and Canada Curriculum - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-05 : Permanent English Voters' List for School Elections - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-06 : Curriculum Development - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021-07 : Addressing the Issue of the Teacher Shortage in Quebec - Quebec Federation of Home and School Associations (QFHSA) (2021)

Resolution 2021 08 : Environmental Awareness - Quebec Federation of Home and School Associations (QFHSA) (2021)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2021)

Jamaica Association of Montreal Newsletter : Apr. - June. 2021 : Vol. 20 - Jamaica Association of Montreal (JAM) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

New Case-MCQ Program Provides Free Monthly Books to Young Readers - Ottier, Audrey; Vidal, Emily (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Neighbours Newsletter : April 2021 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2021)

Annual Report : April 1, 2020 to March 31, 2021 - Quebec English-Speaking Communities Research Network (QUESCREN) (2021)

Early Childhood Session - Cech, Anne-Marie (Montreal Community Forum, 2021)

Youth Entrepreneurship Guide - Fequet, Shelley; Fequet, Latesha; Roberts, Ashley (Coasters Association, 2021)
This guide is intended for young adults between the ages of 18-35. Its purpose is to help guide and support individuals through the process of creating their own business and to identify the resources needed to be successful. The development of this guide was supported by the members of the HOME Committee. Partners represented on the HOME Committee include; Community Economic Development and Employability Committee (CEDEC), Centre de services scolaire du Littoral. Centre lntegre de Sante et de Services Sociaux de la Cote-Nord (CISSS), Coasters Association and the MRC du Golfe-du-Saint-Laurent.

Jamaica Association of Montreal Newsletter : Jan. - Mar. 2021 : Vol. 19 - Jamaica Association of Montreal (JAM) (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

AGM Minutes - Coasters Association (2021)

Guest List : 2021 Annual General Meeting - Coasters Association (2021)

Follow-up Report - Maurice, Cornella (Coasters Association, 2021)

Survey of MCLL Moderator Engagement : Report to the MCLL Council - McGill Community For Lifelong Learning (MCLL) (2021)
In December 2019, Council requested that the Planning Committee create and administer a survey of moderators to inquire about their engagement in the MCLL community in the service of retaining and recruiting moderators. Due to the COVID-19 outbreak and the high-priority burden the pandemic put on various committees, the survey was delayed until late in the Fall 2020 term. This document reports on the survey results and includes, in appendices, the survey questions as well as the detailed results including all comments received by respondents.

Staff : February 2021 - Coasters Association (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Neighbours Newsletter : February 2021 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2021)

February 2021 Federal Pre-Budget Consultation - Townshippers' Association (2021)
For more than 40 years Townshippers’ Association has been at the forefront of community engagement, pursuing its mission to promote the interests of the English-speaking community in Quebec’s historical Eastern Townships, strengthen its cultural identity, and encourage the full participation of the English-speaking population in the community at large. We work on behalf of more than 40, 000 English-speakers who are spread across a region that is geographically larger than Belgium; stretching from Philipsburg in the west to Megantic in the east, and from Inverness in the north to the U.S. border in the south. This brief will provide essential information regarding factors affecting Official Language Minority Community vitality; recent statistics describing the situation of English-speakers in the Historical Eastern Townships (HET), including preliminary data showing the impacts of the COVID-19 pandemic; and conclude with recommendations for consideration in the development of a new federal budget.
Keywords: Official Language Minority Community (OLMC)

Window Onto Local Farming : Être femme en agriculture / Women in Agriculture - Miller, Julie; Lapierre, Carole-Anne (2021)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Impact Report 2020-2021 - 4Korners (2021)

2020-2021 Annual Report: Saint Brigid’s Home Residents’ Committee - CHSLD Saint Brigid’s Home (SBH) (2021)

Agenda: Business Meeting - Coasters Association (2021)

The Coasters Association 27th Annual General Meeting & 32nd Anniversary - Coasters Association (2021)

Annual Report 2021 - Committee for Anglophone Social Action (CASA) (2021)

Community NetLink - Community Health and Social Services Network (CHSSN) (2021)

Activity Report 2020-2021 - Jamaica Association of Montreal (JAM) (2021)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.

Jeffery Hale – Saint Brigid’s Users' Committee Invites You to Have Your Say - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Report to the community : Highlights from 2019-2021 and overview of where we’re headed - Jeffery Hale - Saint Brigid's (JHSB) (2021)

Life without Compromise : Youth Forum 2021 - Kayla; Fequet, Latesha (2021)

Pedagogical Practices: The How of Teaching and Learning - Leading English Education and Resource Network (LEARN) (2021)

Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2021)
Keywords: Official Language Minority Community (OLMC)

Activity Report - Literacy Quebec (LQ) (2021)

Family Literacy Toolkit - Literacy Quebec (LQ) (2021)

Annual Report : 2020-2021 - McGill Community For Lifelong Learning (MCLL) (2021)

Annual Report : 2020-2021 - Megantic English-speaking Community Development Corporation (MCDC) (2021)

Society Pages - Morrin Centre (2021)

Society Pages - Morrin Centre (2021)

Annual Report : Our Collective Impact 2020-2021 - NDG Community Council (NDGCC) (2021)

2nd Annual General Meeting 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report 2020-2021 - Regional Development Network (RDN) (2021)

Annual Report : 2020-2021 - Réseau de l’est de l’île pour les services en anglais (REISA) (2021)

2020/2021 Annual Report - Seniors Action Quebec (SAQ) (2021)

2020-2021 Annual Report - The English Speaking Catholic Council (ESCC) (2021)

Townshippers' Association : 2020-2021 Annual Report - Townshippers' Association (2021)

The Holland Centre Experience : A Community Development Model for Minorities - Walling, Richard (Holland Resources Development Corporation, 2021)
The Holland Centre is a partnership of four public organisations and one private non-profit community organisation that has been successful in creating culturally-appropriate health and social services for a minority community in the province of Quebec, Canada. In June 1999 the J.W. McConnell Foundation awarded a grant to the Holland Centre that allowed it the time and resources necessary to analyse the elements of the centre’s success and develop the tools necessary to assist other linguistic minority communities to develop essential services.

The Yellow Door : 2020-2021 Annual Report / La Porte Jaune : 2020-2021 Rapport annuel - Yellow Door (2021)

Fall Program Book : September - December 2021 - Youth Employment Services (YES) (2021)

Showing up When it Counts : 2021 Annual Report - Youth Employment Services (YES) (2021)

Toujours au rendez-vous : Rapport annuel 2021 - Youth Employment Services (YES) (2021)

Building Bridges : Final Report on the 2019 Consultations : 2019 Consultation with Organizations Serving English-speaking Communities on the Priorities and Orientations of the Secrétariat aux relations avec les Québécois d'expression anglaise - Ravensbergen, Frances (Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA), 2020)
In the fall of 2019, the Secrétariat aux relations avec les Québécois d’expression anglaise (the “Secrétariat”) consulted with its community and institutional stakeholders in a series of 11 sessions. Overall, more than three hundred community leaders representing more than 140 organizations and institutions participated in the consultation, which gave them an opportunity to provide input on priorities and orientations for the Secrétariat.

CLP : Unoriginal - Dawson Alternative School (2020)

Jamaica Association of Montreal Newsletter : Oct. – December 2020 : Volume 18 - Jamaica Association of Montreal (JAM) (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Neighbours Newsletter : December: 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

Aivik - Writers in the Community (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

$40,000 Awarded in Student Leadership Bursaries for the Mauricie/Centre-du-Québec Region - Miller, Julie; Vidal, Emily (2020)

Forum for Youth Insights 2020 - Quebec English-speaking Communities Research Network (QUESCREN) (2020)

Annual Report 2019-2020 - Community Health and Social Services Network (CHSSN) (2020)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Neighbours Newsletter : October 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Jamaica Association of Montreal Newsletter : July – Sept. 2020 : Volume 17 - Jamaica Association of Montreal (JAM) (2020)

AGM Package 2019-2020 - English Language Arts Network (ELAN) (2020)
Keywords: Official Language Minority Community (OLMC)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2020)

Neighbours Newsletter : August 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

10 Innovative Projects to Assist Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2020)

2019-2020 Annual Report : Saint Brigid's Home Residents' Committee - Leger, Valerie (Jeffery Hale - Saint Brigids (JHSB), 2020)
The roles and responsibilities of our Residents’ Committee (shared with the Users’ Committee) are to: 1. Inform users of their rights and obligations. 2. Help improve the quality of living conditions and evaluate the degree of satisfaction with the services at the institution. 3. Defend the collective rights and interests of users or, upon request, the rights and interests of an individual user, before the institution or any competent authority. The SBH Residents’ Committee is overseen by the JHSB Users’ Committee. As president, I therefore attended its meetings to receive and give information of interest to SBH. As committees we strive to work closely with administrators at SBH to ensure our concerns translate into quality services for residents.

39th Annual General Meeting - Voice of English-speaking Quebec (VEQ) (2020)

2020 English-Speaking Community Award Winners - Townshippers' Association (2020)

Newsletter - Coasters Association (2020)

Teenage Vibes - Dawson Alternative School (2020)

Jamaica Association of Montreal Newsletter : Apr. – Jun. 2020 : Volume 16 - Jamaica Association of Montreal (JAM) (2020)

Mesure 17 marche exploratoire : Fielding Walkley - NDG Community Council (NDGCC) (2020)

Neighbours Newsletter : Month of June : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Network News - Quebec Community Groups Network (QCGN) (2020)

[Jeffery Hale - Saint Brigid’s Users’ Committee Annual Report : 2019-2020] - Jeffery Hale – Saint Brigid’s Users’ Committee (Jeffery Hale - Saint Brigids (JHSB), 2020)
The Jeffery Hale – Saint Brigid’s Users’ Committee met nine times from April 2019 to February 2020 in addition to its Annual Meeting on May 8, 2019. The Annual Meeting was held in conjunction with an Information Meeting by the Administration for Saint Brigid’s Residents and families and was well attended. The March 2020 meeting was cancelled because of the Covid19 virus pandemic. Throughout the year the Committee’s meetings were held in the Saint Brigid’s Boardroom because of renovations to the Jeffery Hale Pavilion.

Jamaica Association of Montreal Newsletter : Special Edition: May 2020 : Volume 16.1 - Jamaica Association of Montreal (JAM) (2020)

Fostering the Well-Being of English-Speaking Quebecers Through Community Involvement? : A Statistical Analysis of the Relationship Between Activism and Individual Happiness - Bonin, Pierre-Olivier (Quebec English-speaking Communities Research Network (QUESCREN), 2020)
Scholars of many disciplines have studied Canadian official language minority communities (OLMCs) such as the English-speaking communities in Quebec. One of the most successful research frameworks draws on the notion of vitality. Studies on vitality, be it construed as group vitality (e.g., Bourhis et al. 2019), subjective vitality (e.g., Landry and Allard 1994) or community vitality (e.g., Floch, Abou-Rjeili, and Durand 2017), have provided detailed empirical portraits of OLMCs. While scholars working in the latter area have addressed the many symptoms, causes, and consequences of strong and weak vitality, this working paper will provide empirical insights on a less often studied side of the question. Specifically, the extant literature has addressed the issue of vitality by examining aggregate indicators; this working paper will examine solutions that may improve the well-being of OLMCs at the individual level.
Keywords: Official Language Minority Community (OLMC)

Neighbours Newsletter : April 2020 : Neighbours Regional Association of Rouyn-Noranda - Neighbours Regional Association of Rouyn-Noranda (2020)

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Annual Report : April 1, 2019 to March 31, 2020 - Quebec English-Speaking Communities Research Network (QUESCREN) (2020)

Executive Director's Report : April 2019 to March 2020 - Coasters Association (2020)
This report of activities of the Coasters Association Inc. have been prepared in order to provide the Board of Directors and membership with general information and summary of the work carried out since April 1st, 2019 to March 31st, 2020 (12 months), as outlined in the activities of the contribution agreement of Canadian Heritage.

Social Portrait of the Greenfield Park Borough (Ville de Longueuil) - Corporation de développement communautaire de l’agglomération de Longueuil (2020)

Jamaica Association of Montreal Newsletter : Jan. - Mar. 2020 : Vol. 15 - Jamaica Association of Montreal (JAM) (2020)

Newsletter - Coasters Association (2020)

Westhaven Vision 2020 : A Community Vision for a Healthier, Safer, and More Vibrant Neighbourhood - NDG Community Council (NDGCC) (2020)
In the spring of 2018, the NDG Community Council received funding from the Direction Régionale de Santé Publique de Montréal (DRSP) Mésure 17 programme ‘environnement favorable à la santé’ for a two-year project in Westhaven, a small, physically isolated and so- cio-economically vulnerable neighborhood located in the Montreal borough of Côte-des-Neiges–Notre-Dame-de-Grâce. The Mésure 17 fund was created to support projects with an approach based on the supportive environments model, which considers the built environ- ment as a significant influencer on social inequalities in health status in a community. Westhaven was chosen in large part due to its stark socio-demographic differences from other areas nearby.

Impact Report 2019-2020 - 4Korners (2020)

Profile of Laurentian English-speaking Youth 15-29 - 4Korners (2020)
According to data published by the Institut de la statistique du Québec in 2020, the population living in the administrative regions of the province has significantly changed between 2019 and 2021, being directly affected by the social impacts caused by the COVID-19 pandemic and its implications for out-migration, mobility, workforce attractivity, work/life balance, lifestyle habits and leisure activities. As a result, it is estimated that 632,000 inhabitants were living in the Laurentian region as of July 1, 2020. This represents an increase of 17.7% for the year 2019-2020, which is higher than the average rate across the province (8.5%) for that year. In fact, it is important to highlight that this region presents the largest increase since the outbreak of the pandemic in March 2020.

AGM Minutes : Annual General Report - Coasters Association (2020)

Annual General Meeting : Coastal Summit Series 2020 - Coasters Association (2020)

Annual Report 2019-2020 - Committee for Anglophone Social Action (CASA) (2020)

Annual Report 2020-2021 - Community Health and Social Services Network (CHSSN) (2020)

CAMI’s Annual General Meeting : 2019-2020 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)
The Association was founded in November 1962, shortly after Jamaica’s Independence in August 1962. Our seal of Incorporation was granted in 1970. Since its inception, the Association has grown strong in attracting members. It is recognized as the official organization representing Jamaicans in Montreal at the Federal, Provincial and Municipal levels. We are a member of the United Council for Human Rights and have accompanied delegations and presented briefs to all levels of government. Given our commitment to community development, the Jamaica Association developed our Mission Statement as follows: “To assist in improving and enhancing the quality of life for the Jamaican Community”.

Activity Report 2019-2020 - Jamaica Association of Montreal (JAM) (2020)

[Jeffery Hale - Saint Brigid's Friends' Foundation Annual report 2019-2020] - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid’s (JHSB), 2020)

Jeffery Hale-Saint Brigid's Friends' Foundation Annual Report 2019-2020 - Jeffery Hale – Saint Brigid’s Friends’ Foundation (Jeffery Hale - Saint Brigid's (JHSB), 2020)
The mission of the Friends' Foundation is to raise money to support Jeffery Hale - Saint Brigid's in its quest to provide quality health and social services to all its residents and clients. This report presents the results of the Friends’ Foundation’s projects financed for the year 2019.

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Quebec's Community School Network - Leading English Education and Resource Network (LEARN) (2020)

The Role for Performances in Educational Practices - Leading English Education and Resource Network (LEARN) (2020)

Annual Report 2019/2020 : 40th Anniversary Edition - Literacy Quebec (LQ) (Literacy Quebec, 2020)

Celebrating 40 Years - Literacy Quebec (LQ) (2020)
The year was 1980 and the world was undergoing massive change. CNN launched, the Rubik’s cube went on sale and the Iran-Iraq war began. Closer to home, Quebecers voted in a sovereignty referendum to remain part of Canada, while the sports scene saw the Montreal Canadiens fail in their quest for a fifth consecutive Stanley Cup. But something else historic was also brewing in the province that year: Laubach Literacy Canada-Quebec (LLC-Q), the forerunner of Literacy Volunteers of Quebec, now known as Literacy Quebec.

The Newsletter : Fall 2020: Volume 31, No. 2 - McGill Community For Lifelong Learning (MCLL) (2020)

Memorandum of Understanding Between the School of Continuing Studies and the McGill Community for Lifelong Learning - McGill School of Continuing Studies (2020)

Annual Report : 2019-2020 - Megantic English-speaking Community Development Corporation (MCDC) (2020)

Annual Report : 2019-2020 - NDG Community Council (NDGCC) (2020)

Communications During COVID Time - NDG Community Council (NDGCC) (2020)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2020)

Annual Report : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2020)

2019-2020 Annual Report - The English Speaking Catholic Council (ESCC) (2020)

Townshippers' Association : 2019-2020 Annual Report - Townshippers' Association (2020)

Annual Report - Vision Gaspé-Percé Now (2020)

The Yellow Door : 2019-2020 Annual Report - Yellow Door (2020)

Who We Are - Youth Employment Services (YES) (2020)

Winter/Spring 2020 Program Book : January 2020 - August 2020 - Youth Employment Services (YES) (2020)

Partners In Health - Assistance and Referral Centre (ARC) (2019)

Partners in Health - Centre for Access to Services in English (CASE) (2019)

Voice of Survival - Dawson Alternative School; Writers in the Community (2019)

Humanity is a..... - Writers in the Community (2019)

$1.1 Million Fund to Address Needs of Vulnerable English-speaking Youth and Seniors - Quebec Community Groups Network (QCGN) (2019)

Bill 40 Submission by APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)

Access Programs for Health and Social Services in the English Language : Presentation to NPIs - Prata, Ghislaine (2019)

Brief to Appele Quebec on Bill 40 : an Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Buck, John (Community Economic Development and Employability Corporation (CEDEC), 2019)
The Community Economic Development and Employability Corporation, CEDEC, has been intimately involved over the last twenty-five years in developing and enhancing the vitality of the English-speaking Minority Community of Quebec. CEDEC is committed to improving the economic well-being of communities. It is a hub of innovative research and practice focused on enhancing economic activity that benefits communities through public, private, and civil society collaboration.

Chaotic Masterpiece - Writers in the Community (2019)

Compliation of Creations - Writers in the Community (2019)

Second Home - Writers in the Community (2019)

Four Community Champions Honoured by QCGN : Work of Sen. Joan Fraser, Josh Freed, Martin Murphy, Joshua Arless to be celebrated - Quebec Community Groups Network (QCGN) (2019)

Turn into YES 12 : A Benefit Event and Silent Auction : Le Monastere Cabaret de Cirque - Youth Employment Services (YES) (2019)

Annual Report 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)

Lower North Shore Housing Needs Assessment - Kippen, Kayla (2019)
Communities in rural remote regions often struggle with access to services across the province and other parts of Canada. These access issues are often worsened during times of crisis. A significant problem facing rural communities is the current housing structure for vulnerable people. For example, those requiring palliative care services, or facing mental health and dependency issues, are particularly confronted with issues when trying to secure or obtain stable housing, or access to supportive housing programs and services. In 2017, the federal government announced its first ever National Housing Strategy for Canadians, with a goal of making sure Canadians across the country can access housing that meets their needs and that they can afford. With the witnessed economic downturns, poverty and unemployment rates of the region, it was necessary to investigate whether the Lower North Shore was also providing access to housing that meets the needs of all citizens.

Building Bridges : Activity Report of the Secrétariat aux relations avec les Québécois d’expression anglaise 2017-2019 - Québec. Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA) (2019)
This report provides an overview of the Secrétariat aux relations avec les Québécois d’expression anglaise (SRQEA) from its creation in November 2017 until the end of its first full year of operation in March 2019. The document focuses on the various dimensions of its mandate: community liaison, research, policy development, interdepartmental relations and intergovernmental relations. The purpose of this report is to provide an overview of the objectives, strategies and activities of the Secrétariat to ensure that stakeholders inside and outside government are fully informed of its progress to date.

Moderators’ Handbook : September 2019 - McGill Community For Lifelong Learning (MCLL) (2019)

Notre Dame de Grâce : Community Council By-Laws - NDG Community Council (NDGCC) (2019)

Benefits of QWF Membership - Quebec Writers' Federation (QWF) (2019)

Partners In Health - Assistance and Referral Centre (ARC) (2019)

Annual Activity Report : June 1, 2018 - May 31, 2019 - Literacy Quebec (LQ) (2019)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2019)

Melancholic Bliss - Dawson Alternative School (2019)

No Promises - Dawson Alternative School (2019)

The Struggle is Real - Dawson Alternative School (2019)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Financial Statements - Voice of English-speaking Quebec (VEQ) (2019)

Assessment of the Priority Setting Process for the English-speaking Communities of Quebec (ESCQ) : Guide for the Focus Groups - Canada. Department of Canadian Heritage; Quebec Community Groups Network (QCGN); KSAR & Associates (2019)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands - Community Health and Social Services Network (CHSSN) (2019)
Bright Beginnings is an adapted approach to supporting English-speaking children and families in the Gaspé and Magdalen Islands. It originated through a collaboration between CASA, CAMI and VGPN who began to work with regional and local partners to better adapt programs and services to support English- speaking children 0 to 5 years old and their families. This approach has been adopted by the CHSSN as a provincial framework for English- speaking communities.

Impact Report 2018-19 : English Community Services & Support - 4Korners (2019)

Annual Report 2018-2019 - Committee for Anglophone Social Action (CASA) (2019)

CAMI’s Annual General Meeting : 2018-2019 - Council for Anglophone Magdalen Islanders (CAMI) (2019)

Writers in the Community Program: Keep it Real Make it Real - Dawson Alternative School (2019)

ELAN 15 Year Anniversary Booklet - English Language Arts Network (ELAN) (2019)

Report to the Community : Highlights from 2018-2019 and Overview of Where We're Headed - Jeffery Hale - Saint Brigid's (JHSB) (2019)

A Practitioner's Guide to CLC Extension - Leading English Education and Resource Network (LEARN) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Indicators Toolkit - Leading English Education and Resource Network (LEARN) (2019)

Indicators Toolkit : Guidelines for Selection Indicators and How to Monitor Them in the Short, Medium and Long-Term - Leading English Education and Resource Network (LEARN) (2019)

Understanding Ways of Knowing : Insights and Illustrations - Leading English Education and Resource Network (LEARN) (2019)

Message For Our Veterans - Maurice, Cornella (2019)

McGill Community for Lifelong Learning : Elected Council Members and Committee Chairs - McGill Community For Lifelong Learning (MCLL) (2019)

The Newsletter : Spring 2019: Volume 30, No. 2 - McGill Community For Lifelong Learning (MCLL) (2019)

The Newsletter : Winter 2019: Volume 30, No. 1 - McGill Community For Lifelong Learning (MCLL) (2019)

Annual Report : 2018-2019 - Megantic English-speaking Community Development Corporation (MCDC) (2019)

Annual Report : 2018-2019 - NDG Community Council (NDGCC) (2019)

Report on the 2019 NDG Community Health Forum - NDG Community Council (NDGCC) (2019)
On October 20th 2019, the NDG Senior Citizens’ Council sponsored a community health forum organized in collaboration with the NDG Working Group on Health and the NDG Community Council. The African-Canadian Development and Prevention Network (ACDPN), Hear Entendre Quebec and Prevention NDG were also engaged regularly throughout the process in order to address issues of access and cultural sensitivity in the discussions. The goal of the forum was to inform the residents of NDG and surrounding areas about the resources that exist through institutions supported by the Centre Intégré Universitaire de Santé et de Services Sociaux for the Center-West of Montreal (Hereafter CIUSSS-CODIM), as well as many of the local community organizations, in particular as they relate to health and health access. Further, the event aimed to create a discourse between the health and social service providers, encouraging participants to open a dialogue regarding the gaps in services experienced by residents so that the Working Group on Health could be better informed for future action.

Annual Report / Rapport Annuel 2018-2019 - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN), 2019)
Keywords: Official Language Minority Community (OLMC)

Community Awards 2019 : Call for Nominations - Quebec Community Groups Network (QCGN) (2019)

Innovation in Action / Innovation en action - Quebec Community Groups Network (QCGN) (2019)
The Community Innovation Fund (CIF) has helped Quebec’s English- speaking communities transform social innovation into action through the development of skills. The Fund financed 10 innovative projects that targeted particular needs and priorities of vulnerable English-speaking youth, seniors and newcomers. Each project, in its own way, served to improve job skills or help maintain basic socio-economic security of English-speaking Quebecers. In the following pages, you will learn more about these projects – what they set out to do, what they’ve accomplished and how they served to enhance the vitality of English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

QCGN Community Leadership Awards - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

Annual Report : 2018-2019 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of the Magdalen Islands - Richardson, Mary; Maynard, Hugh; Burke, Helena; Brinklow, Laurie; Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2019)
In recent years, the English-speaking community of the Magdalen Islands has been engaged in a structured approach to community development. This has been guided by knowledge development and mobilization, strategic planning, and partnerships with local stakeholders to develop and implement relevant projects that meet the needs of the community.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Townshippers' Association : 2018-2019 Annual Report - Townshippers' Association (2019)

Vital Communities and Critical Institutions for the Transmission of English-speaking Quebec’s Cultural, Social, and Historical Identity - Townshippers' Association (2019)
This paper will demonstrate how the role of education in a minority language context is much more comprehensive than simply ensuring academic success or instruction in English and is inherently linked to the transmission of its collective history and culture over generations with particular emphasis on the English-speaking community of Quebec (hereafter referred to as the ESCQ), who are struggling to sustain their vitality.
Keywords: Official Language Minority Community (OLMC)

Annual Report - Vision Gaspé-Percé Now (2019)

The Yellow Door : 2018-2019 Annual Report - Yellow Door (2019)

Report of the Planning Committee on the 2018 Members’ Forum - McGill Community For Lifelong Learning (MCLL) (2018)
A Members’ Forum was held on 26 October 2018 to discuss the issue of peer learning at MCLL. The three major findings and the four recommendations are presented here

Selected Papers from the 2018 Conference on Community Education and Development: Perspectives on English-Speaking Blacks and Minorities - Black Community Resource Centre (BCRC) (Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities, 2018)
The Black Community Resource Centre (BCRC) is a growing, resource-based organization that strengthens community capacity by providing professional support to organizations and individuals in need. The Centre is committed to helping visible minority youth rekindle their dreams, and achieve their full potential.We take a comprehensive approach to meet the needs of English-speaking youth. By referring to the “Holistic Project” approach through our community service, we recognize that youth have many needs (e.g., socio-cultural, educational, and economic, etc.) that must be addressed in order for youth to achieve their greatest potential in our society.
Keywords: Official Language Minority Community (OLMC)

NDG Community Strategic Action Plan 2016-2021 : Part III - NDG Community Council (NDGCC) (2018)
This document is the first of three that collectively represent the NDG Community Strate- gic Plan 2016-2021. Part I is a report on the strategic planning and action planning pro- cess and presents the context, tools and outcomes of the NDG Community Strategic Plan. Part II includes annexes to this report with details, tools and other data. Part III presents the Action Plan 2018-2021.

Aesthetics : More Than What it Looks - Dawson School; Writers in the Community (2018)

A New Path - Vanguard School; Writers in the Community (2018)

Outlander : Stories from Inuk Boys: Surusiit Maqitiit Unikausingit - Writers in the Community (2018)

Sippin Makes Me Cry - Writers in the Community (2018)

English-speaking Communities of the Gaspésie-Îles-de-la-Madeleine : A Regional Profile - Vision Gaspé-Percé Now (VGPN) (2018)

Y4Y Quebec Congratulates Executive Committee Member Hayley Campbell for Winning the 2018 Young Quebecers Leading the Way Award - Youth for Youth Québec (Y4Y Québec) (2018)

Turn into YES 12 : A Benefit Event and Silent Auction : Sponsorship Opportunity - Youth Employment Services (YES) (2018)

QCGN to Pay Tribute to Four Remarkable Community Leaders at 10th Anniversary Community Awards Gala - Quebec Community Groups Network (QCGN) (2018)

Partners in Health - Centre for Access to Services in English (CASE) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

ELAN's 14th Annual General Meeting - English Language Arts Network (ELAN) (2018)
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2018)

AGM Issue : June 2018 - Regional Association of West Quebecers (RAWQ) (2018)

The Poetic Motherhood - Writers in the Community (2018)

Inuit Boy Stories : Carving Our Words Into Stone - Writers in the Community Program (2018)

Annual Activity Report : June 1, 2017 - May 31, 2018 - Literacy Quebec (LQ) (2018)
Literacy Quebec provided ongoing support to its members by offering training and assistance via web, email and telephone. The LQ staff fielded and responded to 950+ enquiries and concerns from its membership. They also sent out 30 email updates throughout the year. Members were brought together once in person and once via web-conference for professional developments and networking opportunities.
Keywords: Official Language Minority Community (OLMC)

Don't Judge a Cover - Dawson Alternative (2018)

Understand - Dawson Alternative School (2018)

This Small Town - Harrington School; Writers in the Community (2018)

One Land Divided By Lines Not Seen : Poems by Netagamiou School Secondary IV and V - Netagamiou School (2018)

Growing Between the Cracks - Writers in the Community (2018)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2018)

Visions of Hope - Dawson Alternative School (2018)

Regional Tourism Action Plan for the English-speaking Community of the Gaspé and Magdalen Islands 2018-2023 - Harrison, Kim (Committee for Anglophone Social Action (CASA), 2018)
The Committee for Anglophone Social Action (CASA) works to build and strengthen the vitality of the English-speaking community of the Gaspé Coast This regional tourism action plan has been developed to foster the increased participation in the tourism industry by English speakers and encourage a greater number of English speakers to visit the Gaspé Coast and the Magdalen Islands. The English-speaking community of the region faces many socio-economic challenges as compared to the francophone population. Increased participation in tourism industry would generate social and economic benefits at the individual, organizational and community level. A recent study commissioned by the Community Economic Development and Employability Committee has indicated a high level of interest by American and Ontarian travellers in visiting the attractions of the English-speaking Quebec, as well as the desire to receive English services when visiting the province.
Keywords: Official Language Minority Community (OLMC)

Impact of the 2011-2014 Community Leadership Bursary Program : Adjustments for the future? - Gagnon, Marie-Pierre; Lampron, Amélie (2018)

Eyelash : A Literary Zine - Writers in the Community (2018)

Impact Report 2017-18 : English Community Services & Support - 4Korners (2018)

Strategic Plan 2018-2023 - Coasters Association (2018)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.

Adaptation Initiative Project Guide 2018-2023 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

CAMI’s Annual General Meeting : 2017-2018 - Council for Anglophone Magdalen Islanders (CAMI) (2018)

Main Achievements 2014-2018 - Dialogue McGill (2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)

CLC Extended Model : Learnings & Next Steps from the First 4 Years - Estuaries Learning Consulting Group (Leading English Education and Resource Network (LEARN), 2018)
From January to March of 2018, LEARN undertook an evaluation of the CLC extended model that looked to answer two key questions: 1) Has the CLC extended model been a success, and; 2) What best practices can schools and school boards adopt to effectively introduce the CLC extended model? In asking these questions, LEARN was looking to support two specific types of stakeholders: 1) Schools and school boards wanting to understand the benefits and outcomes of the extended model; and, 2) Schools and school boards wanting a deeper understanding of how to extend effectively. The majority of school boards currently have CLCs that have been extended models for a short duration. The data presented here reflects this, as it responds to question two more fully. It will be useful to do a further evaluation in a few years’ time to gather more precise data on the success of the model, once schools have engaged with it for a longer period.

David Graham - Member of Parliament for Laurentides-Labelle - Graham, David (2018)

Project Report : Presented by Lower North Shore Housing Corporation - Kippen, Kayla (2018)
The Corporation d’habitation de la Basse-Cote-Nord, or Lower North Shore Housing Corporation (LNSHC), was legally registered as a non-profit organization in October 2018. The Housing Corporation was an initiative presented by the Coasters Association, and other organizations, to develop an affiliate corporation that would manage housing programs and services for the region. Over the past year of the project, there have been many achievements and challenges. There has been a great amount of effort put in by all those associated with this project. It is clear that the Housing Corporation is an important initiative to the representatives and citizens of the Lower North Shore. It is for this reason that we must continue to work towards exploring funding avenues to support the continuance of this project.

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Teaching and Learning with Stories - Leading English Education and Resource Network (LEARN) (2018)

Message For Our Veterans - Maurice, Cornella (2018)

The Newsletter : Fall 2018: Volume 29, No. 3 - McGill Community For Lifelong Learning (MCLL) (2018)

Annual Report : 2017-2018 - NDG Community Council (NDGCC) (2018)

Rapport annuel : 2017-2018 - NDG Community Council (NDGCC) (2018)

Annual Report : 2017-2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Townshippers' Association : Annual Report 2017-2018 - Townshippers' Association (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

The Yellow Door : 2017-2018 Annual Report - Yellow Door (2018)

Forecaster - Coasters Association (2017)

Flowers : An Anthology - Dawson Alternative; Writers in the Community (2017)

General By-Laws of The 4 Korners Family Resource Centre - 4Korners (2017)

QCGN Project to Involve Youth in Canada's Sesquicentennial - Quebec Community Groups Network (QCGN) (2017)

Turn into YES 12 : A Benefit Event and Silent Auction : Sponsorship Opportunity - Youth Employment Services (YES) (2017)

Five Inspiring Community Leaders to be Honoured by QCGN - Quebec Community Groups Network (QCGN) (2017)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Annual General Meeting of West Quebecers : 2016-2017 - Regional Association of West Quebecers (RAWQ) (2017)

The Mother Hood - Dawson Alternative School (2017)

Annual Activity Report : June 1, 2016 - May 31, 2017 - Literacy Quebec (LQ) (2017)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once via conference call for professional development and networking opportunities. Through a PACTE funded project, Literacy Quebec was able to develop tools to strengthen its network. The project allowed us to examine new ways of promoting literacy and explaining the issues surrounding low literacy to the general public. The project also enabled the organization to engage more volunteers and pilot a database to track volunteers, supporters, members, etc.

[Quality of Life Conference] - NDG Community Council (NDGCC) (2017)

Poetry - Perspectives I (2017)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2017)

Lower North Shore Collective Impact Forum - Coasters Association (2017)
In April 2017, the Commission Scolaire du Littoral and Community Learning Centres hosted a Lower North Shore training forum. The goal of this regional training forum was to provide an opportunity for participants to learn a method of working together called “Collective Impact”. Collective impact is an advanced method of collaboration that teaches participants how to work together to solve large complex problems so that schools and communities may thrive, developing shared success and shared leadership. Complex problems require engagement and collaborative leadership of stakeholders from across all sectors and all levels of the community leadership including i.e. government leaders, funding agencies, schools, hospitals, the private sector, the not-for-profit sector, community organizers and community members.

Health and Social Services Community Leadership Bursary Program : Annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the second annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program.1 It aims to present data related to bursaries awarded for the 2014-2017 period, based on data collected during the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. The report also provides a profile of graduate recipients for whom post- graduation follow-up was required during the period covered. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Health and Social Services Community Leadership Bursary Program : Bi-annual report - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2017)
This document is the third bi-annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program. This report aims to present data related to bursaries awarded for the 2014-2017 period, taking into account the recipients’ situation as of the second semester of the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Indigenous Education : Walking on Both Sides of the River - Advisory Board on English Education (2017)
Worldwide research has identified low school achievement levels among students from Indigenous cultures and there is a gradual movement to improve their situation. The Truth and Reconciliation Commission (TRC) of the Canadian government has provided the impetus for the provinces to examine their practices and the Advisory Board on English Education (ABEE) congratulates the Minister of Education, Recreation and Sports for joining this initiative. The research literature and the media have identified a broad range of issues affecting the success of Indigenous children in schools. Some of these issues, such as the remoteness and inaccessibility of the communities, poverty, the scarcity and high cost of food, poor housing, and infrastructure problems, are outside the scope of educational solutions, although they combine to have a profound effect on educational outcomes. Social and medical services must be called upon to improve the circumstances that contribute to the educational success of Indigenous students, and we hope this will be facilitated in Québec by the provincial government’s Aboriginal Social Development Action Plan. Yet education is fundamental to any potential solution to Indigenous concerns and problems, and any changes to the situation of the 100 000 Indigenous people of Québec must start with the younger generation. Many of the issues affecting the students and their success or failure in school can be addressed by the school system and this brief will identify some of them. In no way is this brief a prescription to “cure problems” in the Indigenous school system, so it does not contain recommendations, unlike most ABEE briefs. Rather, we will identify some of the issues that might contribute to the discussion of Indigenous education in Québec. We hope that some of the observations and recommendations we have made in earlier briefs regarding the Anglophone school system will be useful additions to the conversation, even though our perspective is influenced by differences between cultures and long-standing problems within Indigenous school systems.

Spring Newsletter - Regional Association of West Quebecers (RAWQ) (2017)

The Network Model : Influencing Public Policy for Social Change - Community Health and Social Services Network (CHSSN) (2017)
The case studies being presented in today demonstrate that the development principles are at work every day and are now being pressed into new areas of action. The values underpinning the network model include promoting the identity of our communities, promoting social inclusion and advocating for equity in the broader society in its treatment of communities. These values can support network strategies to enter the “next level” of participation in societal initiatives setting broad policy goals. The reward for such effort can be societal recognition that the programs that define Quebec’s commitment to social progress also include our communities.

The CLC Guidebook : Steps to Development - Smith, William J.; Leading English Education and Resource Network (LEARN) (2017)

Annual Report : 2016-2017 - 4Korners (2017)

Plan d'action touristique Basse-Côte-Nord du Québec / Lower North Shore Tourism Plan - Coasters Association (2017)

2016-2017 Funded Projects - Dialogue McGill (2017)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Fostering Health and Well-Being in Education - Leading English Education and Resource Network (LEARN) (2017)

Teaching With Technology : Pedagogical Possibilities and Practicalities - Leading English Education and Resource Network (LEARN) (2017)

Annual Report : 2016–2017 - NDG Community Council (NDGCC) (2017)

NDG : A snapshot : Quality of life conference / NDG : Un aperçu : 2017 conférence sur la qualité de vie - NDG Community Council (NDGCC) (2017)

Rapport annuel : 2016–2017 - NDG Community Council (NDGCC) (2017)

Annual Report / Rapport annuel 2016-2017 - Quebec Community Groups Network (QCGN) (2017)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2017)

Annual Report : 2016-2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2016/2017 - Townshippers' Association (2017)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

Fall 2017 : Program Book : September 2017 - December 2017 - Youth Employment Services (YES) (2017)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Van'Sistions : Awesome Writers - Vanguard School; Writers in the Community (2016)

QCGN Appearance before the House of Commons Standing Committee on Official Languages - Quebec Community Groups Network (QCGN) (2016)

Network News - Quebec Community Groups Network (QCGN) (2016)

Health and Social Services Community Leadership Bursary Program : Bi-annual report fall 2016 - Gagnon, Marie-Pierre; Lampron, Amélie (Dialogue McGill, 2016)
This document is the second annual report on the monitoring of the McGill Health and Social Services Community Leadership Bursary Program.1 It aims to present data related to bursaries awarded for the 2014-2017 period, based on data collected during the 2016-2017 academic year, outlining their distribution by region and other variables such as level of study, program of study, and recipients’ medium-term intentions. The report also provides a profile of graduate recipients for whom post- graduation follow-up was required during the period covered. Since this is not a research or evaluation report, data presented in the report are merely descriptive.

Awards Recognize Exceptional Community Leaders - Quebec Community Groups Network (QCGN) (2016)

The Community Learning Centre Initiative : Framework for Action - Smith, William J. (Leading English Education and Resource Network (LEARN), 2016)
In the province of Quebec, English language-minority communities do not always have equitable access to education, health and/or social services. This challenge is particularly acute for English educational institutions and communities, especially in those regions where Anglophones make up a small percentage of the total population and the English school is the only English- language public sector institution in the community. The Community Learning Centre (CLC) Initiative helps to address this gap by building partnerships between English schools and organizations/institutions in their communities. These partnerships, facilitated by a Community Development Agent (CDA), leverage resources that benefit students, their families and the broader community. Recognizing the value of the CLC Initiative, the Association of Directors General of English School Boards of Québec (ADGESBQ) has supported its development since its inception.

ELAN's ACE Initiative TEST! Projects Applicant Guide - Armeni, Virginia; Huff, Christie; Knowles, Paula; English Language Arts Network (ELAN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Keeping the Door Open for Young English-speaking Adults in Québec : Language Learning in English Schools and Centres - Advisory Board on English Education (2016)
During a committee hearing in April 2015, Premier Philippe Couillard responded to a question from Mr. David Birnbaum (MNA for D’Arcy-McGee) about “what our government has done and plans to do to ensure that young anglophone Quebecers are full and valued participants in building our future,” by saying that he wanted to hear from the English-speaking community. About the same time, then-Minister of Education Bolduc asked the Advisory Board on English Education (ABEE) to advise him on how to encourage English-speaking youth to remain in Québec. In May 2016, Premier Couillard identified the English educational sector as a model for the system as a whole, and the Board proposed some reasons for this success in its most recent brief. It should be noted that students in the English sector achieve this success while receiving instruction in two languages from kindergarten onward. The ability to function in two languages is recognized as a crucial socio-economic skill for young Anglophones, and has an impact on their decision whether or not to stay in Québec. How can the education system contribute to developing this skill? This brief is respectfully presented to the Minister of Education with recommendations that respond to this question.

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)

The English Speaking Catholic Council: The Thirty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (2016)

Tree of Life : Poetry Anthology - The Ett LadyZ (2016)

Annual Activity Report : June 1, 2015 - May 31, 2016 - Literacy Quebec (LQ) (2016)
Literacy Quebec continued to provide support to its members by offering training and assistance via web, email and telephone. Members were brought together once in person and once online via web-conference for professional development sessions and networking opportunities.

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2016)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2016)
Health promotion is an activity that community organizations can adopt to enhance visibility and credibility in their communities. Health promotion activities can respond to real needs of different groups and create opportunities to engage the public system with the community organization and the constituencies it serves. For the public network, a community organization that has established a health promotion role has the potential to become a prime partner in helping an institution better serve its target population. In recent years, community networks have developed health promotion programs that have reached thousands of community members and can now demonstrate positive results. The Forum will discuss how this development is resulting in promising and best practices, and inspiring a range of public and community interests to engage in health promotion for English-speaking communities.

Literary and Historical Society of Quebec : General By-Laws - Morrin Centre (2016)

Tourism Marketing Plan Lower North Shore Plan / Plan marketing touristique de la Basse-Côte-Nord - Coasters Association (2016)
The tourism marketing analysis of the Lower North Shore was developed by the Lower North Shore (LNS) Steering Committee along with the previous studies and plans developed by the Quebec Labrador Foundation (QLF), the Local Development Center (CLD), Coop Voyages CoSte and the Regional Tourism Association (ATR). This project will also be carried out in collaboration with these organisations as well as the Coop Solidarité Bioproduits (CSB) and Destination Labrador. This strategic plan will help to identify new innovative opportunities for tourism business development in line with Canada’s tourism strategy. The plan will be presented to an Advisory Committee, the Lower North Shore (LNS) Steering Committee, Industry Canada and LNS/Labrador partners.

Annual Report : 2015-2016 - 4Korners (2016)

English Language Services Directory: Laurentians Region : 2016 - 4Korners (2016)

2015-2016 Funded Projects - Dialogue McGill (2016)

Artful Inquiry : Transforming Understanding Through Creative Engagement - Leading English Education and Resource Network (LEARN) (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

Literature Review - Mulligan, Marleen (Council for Magdalen Islanders (CAMI), 2016)
Small, rural and remote regions around the world are transforming due to forces outside of their control such as globalization, neoliberalism and climate change. While often characterized as being in a state of decline due to dwindling populations and employment opportunities, this literature review reveals that numerous small communities are finding ways to capitalize on these forces of change. The review focuses on regions similar to the Magdalen Islands – situated in the western world, shaped by colonial powers, and relatively well off. The common pattern found among the successful cases is a development approach that is internally focused, builds on existing assets (human, physical and intangible) and is scale appropriate with results that are, therefore necessarily unique to each community. These cases all include senior government support, especially in the form of funding, and in some instances, capacity building, that allows community members to carry the torch and take up the work of revitalizing their community in the ways they deem appropriate.

Annual Report : 2015–2016 - NDG Community Council (NDGCC) (2016)

Rapport annuel : 2015–2016 - NDG Community Council (NDGCC) (2016)

Annual Report / Rapport annuel 2015-2016 - Quebec Community Groups Network (QCGN) (2016)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2016)

Ahuntsic Cartierville : English-speaking Population 2016 / Ahuntsic Cartierville : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Anjou : English-speaking Population 2016 / Anjou : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Annual Report : 2015-2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Mercier Hochelaga-Maisonnneuve : English-speaking Population 2016 / Mercier Hochelaga-Maisonnneuve : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Montréal-Nord : English-speaking Population 2016 / Montréal-Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rivière-des-Prairies and Pointe-aux-Trembles : English-speaking Population 2016 / Rivière-des-Prairies and Pointe-aux-Trembles : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie l'Est : English-speaking Population 2016 / Rosemont-La Petite-Patrie-l-est : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie Nord : English-speaking Population 2016 / Rosemont La Petite-Patrie Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Laurent : English-speaking Population 2016 / Saint-Laurent : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Léonard : English-speaking Population 2016 / Saint-Léonard : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Villeray–Saint-Michel–Parc-Extension : English-speaking Population 2016 / Villeray–Saint-Michel–Parc-Extension : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Focus Group Findings 2015-2016 - Seniors Action Quebec (SAQ) (2016)

2017-2018 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Strategic Priorities Forum (Quebec Community Groups Network (QCGN), 2016)
In September 2011, the Quebec Community Groups Networks launched The Strategic Priorities Forum, a standing five-year cyclical process to identify common priorities ensuring a vital and sustainable future for Quebec’s English-speaking communities and to collectively pursue enabling strategies to achieve community goals over five years. In this capacity, the QCGN established a nine-member Priority Setting Steering Committee (PSSC), a permanent Committee of QCGN’s Board of Directors, to assist the community with the governance of the Strategic Priorities Forum.

Annual Report / Rapport annuel - Vision Gaspé-Percé Now (2016)

Annual Report 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Community Consultation 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

Partner Survey 2015-2016 - Voice of English-speaking Quebec (VEQ) (2016)

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

Newsletter - Westhaven Neighborhood Committee (2016)

Newsletter - Westhaven Neighborhood Committee (2016)

Fall 2016: Program Book : September 2016 - December 2016 - Youth Employment Services (YES) (2016)

Gunshots from the Inside - Writers in the Community (2015)

Always Leading From the Front, Alexander Gordon Wins Youth Leadership Award - Quebec Community Groups Network (QCGN) (2015)

Goldbloom Award Winners Bechervaise, Briand, Gatre Guemiri and Orr Know How To Get Things Done - Quebec Community Groups Network (QCGN) (2015)

New Award to Recognize Up and Coming Community Leaders - Quebec Community Groups Network (QCGN) (2015)

Quebec Community Groups Network Celebrates 20th Anniversary - Quebec Community Groups Network (QCGN) (2015)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

The Build - Richardson, Mary (Council for Magdalen Islanders (CAMI), 2015)
This case study presents a project being implemented in the Baiedes-Chaleurs, Quebec, by which a group of elementary and high school students are building a sailboat with a teacher. They have the support of a broad range of community, institutional and non-for-profit partners who believe, like them, that a challenging project can have positive outcomes both inside and outside the classroom.

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report - Qu'anglo (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report : Executive Summary - Qu'anglo (2015)

QCGN Seeks Exceptional Individuals Who Contribute to Vitality of English-Speaking Community - Quebec Community Groups Network (QCGN) (2015)

ELAN to be Represented on Matv Advisory Committee - English Language Arts Network (ELAN) (2015)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

Quebec Youth Lead the Way to Sesquicentennial Celebrations - Quebec Community Groups Network (QCGN) (2015)

Portrait of the English-speaking Community of Rouyn-Noranda - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Neighbours and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et des services sociaux (CISSS), the city of Rouyn-Noranda (Villes et villages en santé) and the local English school, Noranda School. Neighbours is a non-profit community organization established to serve the Englishspeaking population of the Rouyn-Noranda area through facilitating information sharing, defending the right of access to service in English and organizing social and cultural events. Neighbours is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Rouyn-Noranda in order to address the issues it faces.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme).

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

Annual Report : 2014-2015 - 4Korners (2015)

2014-2015 Funded Projects - Dialogue McGill (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

Building School-Community Partnerships : Together We can Make a Difference : CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

Professional Development in Education : Pushing the Boundaries of Possibility - Leading English Education and Resource Network (LEARN) (2015)

Teacher Research : Integrating Action, Observation, and Reflection - Leading English Education and Resource Network (LEARN) (2015)

Message For Our Veterans - Maurice, Cornella (2015)

Annual Report : 2014–2015 - NDG Community Council (NDGCC) (2015)

Annual Report / Rapport annuel 2014-2015 - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)

The English-speaking Population of des Collines-de-l'Outaouais : a Community Portrait - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed by Connexions and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre intégré de santé et de services sociaux des Collines de l’Outaouais (CISSSO). Connexions (the Connexions Resource Centre) is a not-for-profit community organization whose mission is to serve and promote the health, well-being and vitality of the English-speaking population of the Outaouais. It is committed to strengthening networks within the English and French speaking population as well as encouraging community development initiatives.

Annual Report 2014-2015 - Voice of English-speaking Quebec (VEQ) (2015)

Follow Your Fiction : A Poetry Anthology - Writers in the Community (2015)

Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Turn into YES 8 : A Benefit Event and Silent Auction: Sponsorship Opportunity - Youth Employment Services (YES) (2014)

Hughes, Maldoff and Sharp to Receive Goldbloom Awards for Community Contributions - Quebec Community Groups Network (QCGN) (2014)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

Community Learning Centres : Changing Lives and Communities : 2013-2014 Annual Report of CLC Activities : September 2014 - Leading English Education and Resource Network (LEARN) (2014)

Celebrate the English Language Arts Network's 10th Anniversary : ELAN Marks Tenth Year of Creating Stronger Networks for Quebec's English-speaking Artists - English Language Arts Network (ELAN) (2014)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

QCGN is Looking for a Few Good Men and Women - Quebec Community Groups Network (QCGN) (2014)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2014)

Community in Movement Forum - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

McGill Community for Lifelong Learning : Operating Rules - McGill Community For Lifelong Learning (MCLL) (2014)

Building Communities Together : Laurentians, Outaouais, Quebec Region - Seniors Action Quebec (SAQ) (2014)

Annual Report : 2013-2014 - 4Korners (2014)

Our Story : The New Carlisle Community Learning Centre Developmental Evaluation Report - Chatterton, Tammy; Legault, Emma (Leading English Education and Resource Network (LEARN), 2014)
The New Carlisle Community Learning Centre (NCHS CLC) is one of 37 community schools in Quebec. We are located in a small town on the Gaspesian Peninsula. Many people refer to the location as The Baie Des Chaleur. Our vibrant CLC is located in the town of New Carlisle, within New Carlisle High School. The centre was established to encourage lifelong learning by facilitating access to services and offering support to families, students and community members. The founders believed that a CLC would bridge the noticeable gaps in rural communities like ours, balancing the playing field so that our community would have the same opportunities as more fortunate and larger areas. Therefore, the CLC’s main goal is to link partners together to create a culture of lifelong learning that enhances the capacity of the population to live in healthy vibrant communities.

2013-2014 Annual Report - Cote des Neiges Black Community Association (CDNBCA) (2014)
Striving for excellence since 1972, our organization’s vision and mission is focused on helping Black Canadian families rise above structural inequalities and systemic discrimination. Through our programs and services now more than ever before, we are ready to reaffirm and remember the contribution of Montreal’s Black communities to this society and celebrate our identity and heritage. It is time to allow our unique strengths to become louder than our weaknesses and take strategic steps towards better and sustainable futures. It is time to take care of ourselves, support each other and empower our community to overcome the forces that impede individuals to gain fair access to resources and opportunities. Together we can rewrite our legacy.

Centennial CLC Year 3 Evaluation : Taggin' Our Success! - Elston, Cindy (Leading English Education and Resource Network (LEARN), 2014)
Welcome to Centennial’s Community Learning Centre (CLC) Year 3 evaluation report! In these pages you will find highlights of an evaluation carried out between January-May of 2014. We looked at outcomes of key programs and how they relate to achieving our overall mission and mandate. We designed questions using our Theory of Change (ToC), which has six result areas including the two we focused on this year, Student Success and Community Engagement.

Inclusive Education : Socially Just Perspectives and Practices - Leading English Education and Resource Network (LEARN) (2014)

Annual Activity Report : June 1, 2013 - May 31, 2014 - Literacy Quebec (LQ) (2014)

PACTE Project 2013-2014 : The Power of an Online Presence, a Skill to be Harnessed. - Literacy Quebec (LQ) (2014)
The following project has been completed by Literacy Quebec by a grant from Opération Projets PACTE As a provincial organization, Literacy Quebec’s mandate is to support community-based literacy organizations that provide service to English-speaking adults in Quebec, through training, networking and professional development.

Annual Report : 2013–2014 - NDG Community Council (NDGCC) (2014)

NDG Community Strategic Plan 2013-2016 - NDG Community Council (NDGCC) (2014)

Westhaven Sector NDG Montreal - NDG Community Council (NDGCC) (2014)
The Westhaven sector is one of the four identified vulnerable sectors in Notre-Dame de Grace. Saint- Jacques and Sherbrooke Street on the East and West and West Broadway and Connaught on the North and South side bind this neighbourhood. The NDG Community Council approached various stakeholders and key actors within the community including residents, volunteers, employees and private storeowners in order to voice their concerns and visions for Westhaven.

Annual Report / Rapport annuel 2013-2014 - Quebec Community Groups Network (QCGN) (2014)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2014)
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2014)

Annual Report : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Annual Report 2013-2014 - Voice of English-speaking Quebec (VEQ) (2014)

Western Quebec Literacy Council: Annual Report: 2013-2014 - Western Quebec Literacy Council (2014)

Winter/Spring 2014 Program Book - Youth Employment Services (YES) (2014)

ELAN's Guy Rodgers Elected for Another Term on Culture Montréal Board - English Language Arts Network (ELAN) (2013)

Strategic Plan 2012 - 2015 : Summary Document - Jeffery Hale - Saint Brigid's (JHSB) (2013)

Robinia Goodwin, Judy Martin, and Kevin Tierney Honoured for Outstanding Contributions to English-speaking Quebec - Quebec Community Groups Network (QCGN) (2013)

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

Community Learning Centres : Changing Lives and Communities : Annual Report of Activities : September 2013 - Leading English Education and Resource Network (LEARN) (2013)

2013-2018 Strategic Plan - Quebec Community Groups Network (QCGN) (2013)
English-speaking Quebec is a diverse, confident, recognized and respected national linguistic minority that actively participates in and contributes to the social, economic, cultural and political life of Quebec and Canadian society.
Keywords: Official Language Minority Community (OLMC)

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2013)

Community Portrait : St. Léonard - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2013)

Community Portrait : Laval - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Report : Future Forum of the English-speaking Community - Future Forum of the English-speaking Community (Voice of English-speaking Quebec (VEQ), 2013)
The Future Forum was held on November 24th, 2012 from 9 am - 2 pm at Eastern Québec Learning Center in Quebec City, Québec. The purpose of the event was to share opinions on the current state, needs and challenges of the English-speaking community while generating a shared vision for our future.

Annual Report : 2012-2013 - 4Korners (2013)

Early Childhood Education : Successes and Challenges - Leading English Education and Resource Network (LEARN) (2013)

Teaching and Learning in the Digital World : Possibilities and Challenges - Leading English Education and Resource Network (LEARN) (2013)

Annual Activity Report : June 1, 2012 to May 31, 2013 - Literacy Quebec (LQ) (Literacy Quebec, 2013)

Annual Report : 2012–2013 - NDG Community Council (NDGCC) (2013)

Annual Report / Rapport annuel 2012-2013 - Quebec Community Groups Network (QCGN) (2013)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

Annual Report 2012-2013 - Voice of English-speaking Quebec (VEQ) (2013)

Biding Our Time with Rhymes - Writers in the Community (2013)

Winter/Spring 2013 Program Book - Youth Employment Services (YES) (2013)

The Truth of Change - Elizabeth House; Quebec Writers' Federation (QWF) (2012)

It's Raining Ducks (If You Know What I Mean) ;) - Vanguard Intercultural School; Quebec Writers' Federation (QWF) (2012)

Super Ultra Mega Vanguard Poetry Book - Vanguard Intercultural School; Quebec Writers' Federation (QWF) (2012)

Community Portrait : Sept-Îles - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.

Housing in Notre-Dame-de-Grace : A Portrait of the Issues, Resources and Services Affecting the Community - Pero, Bonnie (NDG Community Council (NDGCC), 2012)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2012)

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Annual Report : 2011-2012 - 4Korners (2012)

Strategic Plan 2012-2017 - Coasters Association (2012)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.

Creativity : Insights, Directions, and Possibilities - Leading English Education and Resource Network (LEARN) (2012)

Informal Learning : Flexible Contexts and Diverse Dimensions - Leading English Education and Resource Network (LEARN) (2012)

Annual Report : 2011–2012 - NDG Community Council (NDGCC) (2012)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2012)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

Annual Report 2011-2012 - Voice of English-speaking Quebec (VEQ) (2012)

In Other Shoes - 9B, Vanguard; Writers in the Community (2011)

9th Quebec Employment Service Providers Conference : The Greatest Challenges and Best Practices of Employment Service Professionals - Youth Employment Services (YES) (2011)

Intonation - Quebec Writers' Federation (QWF); The Centre for Literacy of Quebec (CFL) (2011)

Community Health Education Program (CHEP) : 2010-2011 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2011)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2011)

Annual Report : 2010-2011 - 4Korners (2011)

Public Health Action Plan for the English-Speaking Community in the Capitale-Nationale Region 2011-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2011)
Saint Brigid’s – Jeffery Hale Hospital’s Public Health Action Plan for the English- Speaking Community in the Capitale-Nationale Region is in keeping with the Plan d’action regional (PAR) en santé publique 2009-2012 (regional public health action plan) developed by the Agence de la santé et des services sociaux de la Capitale-Nationale (Agence). To ensure viable results for our efforts aimed at improving the health and well-being of the English-speaking community, we thought it relevant to begin by presenting an updated portrait of the English-speaking community in the CNR. This portrait allows us to identify the various needs of the community, as well as its health determinants and indicators, and take stock of its ongoing evolution. This description is followed by a detailed presentation of Saint Brigid’s – Jeffery Hale Hospital’s prevention and health promotion Service Offer.

Inquiry : Perspectives, Processes and Possibilities - Leading English Education and Resource Network (LEARN) (2011)

Mind, Brain, and Education : Implications for Educators - Leading English Education and Resource Network (LEARN) (2011)

Annual Report : 2010–2011 - NDG Community Council (NDGCC) (2011)

Annual Report / Rapport annuel 2010-2011 - Quebec Community Groups Network (QCGN) (2011)

Annual Report / Rapport annuel 2011-2012 - Quebec Community Groups Network (QCGN) (2011)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2011)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2010-2011 - Voice of English-speaking Quebec (VEQ) (2011)

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

November 2010 : Anniversary Newspaper - Literacy Volunteers of Quebec (2010)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

Presentation to the Standing Senate Committee on Official Languages - Gignac, Jean-Sébastien (2010)

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

Diverse Expressions : A Collection Of Poems - The Women Of Les Maisons Transitionnelles O3 (2010)

Community Health Education Program (CHEP) : 2009-2010 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2010)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2010)

Annual Report : 2009-2010 - 4Korners (2010)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Perspectives on Education : Voices of Eminent Canadians - Leading English Education and Resource Network (LEARN) (2010)

Poetry and Education : Possibilities and Practices - Leading English Education and Resource Network (LEARN) (2010)

[Annual Report 2009-2010] - NDG Community Council (NDGCC) (2010)

Annual Report / Rapport annuel 2009-2010 - Quebec Community Groups Network (QCGN) (2010)

The Sheila & Victor Goldbloom Distinguished Community Service Award - Quebec Community Groups Network (QCGN) (2010)
Keywords: Official Language Minority Community (OLMC)

Annual Report 2009-2010 - Voice of English-speaking Quebec (VEQ) (2010)

YES Fundraising Event Taps into the Rhythms of Montreal - Youth Employment Services (YES) (2009)

The Implementation of Part VII : Community and Social Stakeholders' Perspectives - Palmer, Lise; Tomlinson, Patrick (2009)
During the summer of 2009, OCOL commissioned a team of independent researchers to report on the implementation of Part VII by consulting community and social stakeholders. The goal was to sound out their perception of community vitality, along with their take on the way in which federal institutions fulfill their obligations. More than 175 persons were interviewed and expressed their views across Canada. A report was written for each of the following regions: 1) Atlantic Region; 2) Quebec; 3) Ontario; 4) Manitoba and Saskatchewan; and 5) Alberta, British Columbia, Yukon, Northwest Territories and Nunavut. Another researcher wrote a report after having consulted key stakeholders who promote linguistic duality and second official language learning.

Getting Motivated & Staying Focused - Youth Employment Services (YES) (2009)

QCGN Announces Winners of Sheila and Victor Goldbloom Distinguished Community Service Awards - Quebec Community Groups Network (QCGN) (2009)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2009)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-Newsletter : July 2009 - Youth Employment Services (YES) (2009)

The Twenty-Eighth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2009)

Community Health Education Program (CHEP) : 2008-2009 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2009)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

YES E-Newsletter : June 2009 - Youth Employment Services (YES) (2009)

YES E-Newsletter : May 2009 : Volume 1 : Issue 5 - Youth Employment Services (YES) (2009)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2009)

YES E-News : April 2009 - Youth Employment Services (YES) (2009)

YES E-News : March 2009 - Youth Employment Services (YES) (2009)

Creating Spaces for Young Quebecers : Strategic Orientations for English-speaking Youth in Quebec - Quebec Community Groups Network (QCGN) (2009)
Over the past decades, Francophones in Quebec have taken formal steps to preserve and promote their language and culture. To most English-speaking youth growing up in Quebec today, this makes sense and we agree that steps should be taken to protect Quebec’s uniqueness in North America. However, young English-speakers living in Quebec - from Montreal to the North Shore to the Gaspé - face their own set of unique challenges. In small English-speaking pockets scattered throughout the province, young English-speakers struggle to become bilingual, access services, create strong ties with their communities, participate in Quebec society and define their own identities. The members of the Quebec Community Groups Network (QCGN) Youth Standing Committee have worked together over the last year to ensure that this document represents the perspectives of as many youth as possible from a wide array of regions and backgrounds. We have also worked to ensure that the process has been directed by youth and that the voices we have heard are heard by others as well. This is the first time that a significant percentage of English-speaking youth in Quebec have come together from across many regions to address the barriers young people face. It has been exciting to discuss our Quebec roots, our desire to remain in this province and our willingness to move past the linguistic tensions of previous generations. In consultations across eight regions, followed by a provincial forum, we have generated strategies for moving forward together. This document outlines strategies that youth have recommended to help achieve our collective vision for English-speaking youth in Quebec. We encourage the QCGN to work towards this vision for English-speaking youth in Quebec in collaboration with community partners, all levels of government and Francophone organizations.
Keywords: Official Language Minority Community (OLMC)

Curriculum : Issues and Innovations - Leading English Education and Resource Network (LEARN) (2009)

Literacy : Multiple Perspectives and Practices - Leading English Education and Resource Network (LEARN) (2009)

Community Council Annual Report : 2008 - 2009 / Rapport annuel du Conseil Communautaire : 2008 - 2009 - NDG Community Council (NDGCC) (2009)

Annual Report / Rapport annuel 08-09 - Quebec Community Groups Network (QCGN) (2009)

Annual Report 2008-2009 - Voice of English-speaking Quebec (VEQ) (2009)

A Study of Recruitment and Retention Factors Affecting Immigrants, and Anglophone Newcomers in the Quebec City Region - Voice of English-speaking Quebec (VEQ); Conférence régionale des élus de la Capitale-Nationale (2009)
This study focuses on the trends and community-based responses to in-migration in the Quebec City region. It is specifically concerned with issues pertaining to the local English-speaking community, a group that is vested with the legal and political designation of official language minority community by the federal government of Canada. The issue of in-migration is multifaceted and multidisciplinary. To wade into debates on the patterns and effects of migration over a given territory requires a significant amount of background knowledge from a number of different sources. Moreover, to consider the proper policy responses to migratory patterns, we must pay attention to wider political, sociological, and economic conditions that shape how individuals make decisions, such as why they move to a particular region, how long to stay and when to leave.

Winter/Spring 2009 Program Book - Youth Employment Services (YES) (2009)

French Immersion Teen Camp : Feasibility Study - Newcombe, Vanessa; Roberts, Carla; Griffin, Emily (Coasters Association, 2008)
Living in such an isolated area such as, the Lower North Shore, there is a lack of activities for all ages, but more so for the adolescent age. There are very few activities on the Lower North Shore that directly focuses on teenagers, so teens resort to other activities that result in social problems (i.e. drinking, drugs, vandalism, etc…). Therefore, a French Immersion Teen Camp would provide teenagers with activities and a program that is especially designed for them. Teenagers could have a chance to get away from the social problems and into a program that will nurture and develop a safe and healthy environment in which the teens can improve their health and obtain skills that will assist them in their future lives and also promote and develop their French as a Second Language skill.

2008 Youth Consultation on the Lower North Shore - Buckle, Heidi (Coasters Association, 2008)
The 2008 Lower North Shore Youth Consultation was coordinated to provide a needs assessment of the English-speaking youth on the coast, addressing topics related to youth retention and youth out migration. The projected outcome of the consultation was to empower youth with a collective identity and to encourage greater participation within the Lower North Shore at large.

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2008)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

The Twenty-Seventh Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2008)

CHSSN Telehealth Program & Follow-up Intervention Project : 2007-2008 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2008)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2008)

[Quebec Association for Adult Learning Inc. 2008 Annual General Meeting : Agenda] - Quebec Association for Adult Learning (QAAL) (2008)

The 11th YES Entrepreneurship Conference : March 8/2008 - Youth Employment Services (YES) (2008)

Education and the Arts : Blurring Boundaries and Creating Spaces - Leading English Education and Resource Network (LEARN) (2008)

Leadership in an Era of Change - Leading English Education and Resource Network (LEARN) (2008)

Annual Report 2007-2008 - NDG Community Council (NDGCC) (2008)

Annual Report 2007-2008 - Quebec Community Groups Network (QCGN) (2008)

Annual Report 2007-2008 - Voice of English-speaking Quebec (VEQ) (2008)

Fall 2008 Program Book - Youth Employment Services (YES) (2008)

Winter/Spring 2008 Program Book - Youth Employment Services (YES) (2008)

Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

YES E-News : September 2007 - Youth Employment Services (YES) (2007)

YES Montreal Presents the Meet the Experts Seminar Series : Focus on the Growing Trends in Green Businesses and Social Entrepreneurship - Youth Employment Services (YES) (2007)

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2007)

The 10th Anniversary YES Entrepreneurship Conference : March 3/2007 - Youth Employment Services (YES) (2007)

Report of the Greater Montreal Community Development Initiative Steering Committee : Building Upon Change and Diversity within the English-speaking Communities of the Greater Montreal Region: - Greater Montreal Community Development Initiative (GMCDI) (Quebec Community Groups Network (QCGN), 2007)
In the 30 years since the passage of Bill 101, the nature of the English-speaking communities of the Greater Montreal Area has changed dramatically. The evolution of the largest linguistic minority within a linguistic minority in Canada has resulted in the emergence of certain unique challenges and opportunities. It was to address these issues that the Greater Montreal Community Development Initiative (GMCDI) was launched. This initiative, funded by the Department of Canadian Heritage, is intended to assist the English-speaking communities of the Greater Montreal Area in identifying shared community development challenges and priorities, and the most effective strategies to address them.
Keywords: Official Language Minority Community (OLMC)

Student Engagement in the 21st Century - Leading English Education and Resource Network (LEARN) (2007)

Annual Report 2006-2007 - Quebec Community Groups Network (QCGN) (2007)

Annual Report 2006-2007 - Voice of English-speaking Quebec (VEQ) (2007)

Program Book: Winter / Spring 2007 - Youth Employment Services (YES) (2007)

The Twenty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2006)

A Report on Community Against Drugs : Drug Strategy and Controlled Substance Program by Health Canada - Coasters Association (2006)
The following report describes the activities that were carried out for the development of the program “Community Against Drugs”

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2006)

NTFR : Partnership Forum - Coasters Association (2006)

Annual Report 2005-2006 - Quebec Community Groups Network (QCGN) (2006)

Big Farms, Small Farms : Strategies in Sustainable Agriculture to Fit All Sizes - Maynard, Hugh; Nault, Jacques (Qu’anglo Communications & Consulting, 2005)

Quebec Community Groups Network Welcomes Government of Canada's Investment in Quebec's English-speaking Communities - Quebec Community Groups Network (QCGN) (2005)

The Twenty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2005)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2005)

The Development of an Action Plan to Expand Volunteerism & Leadership on the Lower North Shore of Quebec - Buckle, Heidi (Coasters Association, 2005)
Throughout phase one of this project, a needs assessment study was successfully carried out to identify the needs of the one hundred and thirteen (113) community organizations and twenty-one (21) regional organizations on the coast; along with a volunteer awareness campaign and the building of a strong volunteer base for the fifteen (15) communities of the Lower North Shore of Quebec. This study was then distributed to all the organizations, the working group, the Board of Directors of the Coasters Association and the volunteers who participated in this project. It has been shared with various Quebec Community Group Networks and HRD Community Table groups across the province, along with various federal and provincial government departments. It has been used as a working tool by many organizations on and off the coast.

Annual Report 2004-2005 - Quebec Community Groups Network (QCGN) (2005)

Strategic Plan : 2005-2006 to 2008-2009 - The English Speaking Catholic Council (ESCC) (2005)

Literacy Resource Directory : Prevention Activities in Quebec - Seys, Wendy (Literacy Volunteers of Quebec, 2004)

Report from the Executive Director - Hook, Deborah (Quebec Community Groups Network (QCGN), 2004)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2004)

Brief on Building Local Health and Social Services Networks in Montreal - Allmand, Warren (English Speaking Catholic Council, 2004)
The ESCC was formed in 1980 as a focal point for coordinating community activities among English-speaking Roman Catholics in Montreal and later across all Quebec. In keeping with the mission of the Church and with its teachings on the role of the laity in the modern world, the English Speaking Catholic Council acts in the fields of education, health and social services, social justice and culture to build a sense of community identity and common purpose. We encourage the development of leadership in the community and assist in coordinating human resources in community-based institutions and we endeavour to ensure effective representation before government bodies and on various boards, committees and councils.

Remote Site Information Technology Assessment for the Municipality of Bonne-Esperance Lower North Shore, Quebec - Coasters Association (2004)
Information technologies (computers, Internet, etc.) are an essential component of modern economic development strategies. The Lower North Shore has lagged behind other areas in terms of equipment, infrastructure and human resource capacity for using information technologies as an integral part of their community development efforts (i.e. no hi-speed access.) Recent innovations in this area allow for the reception of hi-speed (broadband) Internet reception via satellite; with establishment of local area networks (LANs) connected to each satellite point-of-delivery, the prospect exists for significant improvements to the information technology capacity of remote locations such as MBE, as well as local revenue generation from service provision once the LAN is established.

The Twenty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2004)

The First English-speaking Community : Global Development Plan 2004-2009 - Grundy, Susan (Quebec Community Groups Network (QCGN), 2003)
The English-speaking Community of Quebec (ESC) represents multiple communities that are diverse, multicultural and multiracial in nature. The Community includes English-speakers who choose to speak or use the English language, for example, for delivery of services. The Community also includes those citizens who identify with, or have an interest in, the English language. The first step taken by the Global Development Planning Steering Committee was to review the need for a Plan to revitalize the English-speaking Community of Quebec. Why are we doing this? Is a Global Development Plan necessary? What do we hope to achieve?

Global Development Plan 2004-2009 : Revitalizing the English-speaking Communities of Quebec - Quebec Community Groups Network (QCGN) (2003)
The English-speaking Community of Quebec (ESC) represents multiple communities that are diverse, multicultural and multiracial in nature. The Community includes English-speakers who choose to speak or use the English language, for example, for delivery of services. The Community also includes those citizens who identify with, or have an interest in, the English language. The first step taken by the Global Development Planning Steering Committee was to review the need for a Plan to revitalize the English-speaking Community of Quebec. Why are we doing this? Is a Global Development Plan necessary? What do we hope to achieve?

Quebec Community Groups Network : Executive Director's Report 2002-2003 - Hook, Deborah (Quebec Community Groups Network (QCGN), 2003)
The year 2002-2003 has once again been an exciting year of growth and deveiopment for the QCGN. Through the many activities undertaken over the past year, we have re-enforced the solidarity among our members and extended our outreach past the QCGN membership into the broader English-speaking community of Quebec.

NDGCC Annual Report : 2002-2003 - NDG Community Council (NDGCC) (2003)

Quebec Community Groups Network By-Laws - Quebec Community Groups Network (QCGN) (2003)

Alliance Quebec Convention - May 23rd and 24th - Alliance Quebec (AQ) (2003)

The Twenty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2003)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2003)

Global Development Plan : Strategy to Revitalize the English-language Minority Communities of Quebec : Sector Plans - Quebec Community Groups Network (QCGN) (2003)
The roots of the English-speaking community in Quebec go back nearly 250 years, and have a historic place in the development of the province. While English-speaking communities traditionally established their own institutions in the areas of religion, education and health and social services, that type of community engagement dissolved to a greater extent with the Quiet Revolution and the emergence of the modern Quebec state. Now, after 30 years of exodus and isolation, the time has come for the English-speaking community to become involved, to re-establish its presence in the policy and program decision-making areas that affect the daily lives of its members.

New Board of Directors Elected at AQ Convention - Alliance Quebec (AQ) (2002)

The Twenty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2002)

Alliance Quebec Convention : May 24-25, 2002 - Alliance Quebec (AQ) (2002)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2002)

Global Development Planning for the English-language Minority Communities of Quebec : Working Group Report Phase 1 : Preparation and Review - Quebec Community Groups Network (QCGN) (2002)
The Global Development Plan (GDP) Working Group has prepared the following report, which presents the conclusions and recommendations of the first phase of the GDP project entitled, Preparation and Review. This report is intended to guide the reader through the Working Group's reflection, discussion and analysis between December 2001 and March 2002.

Global Development Planning for the English-language Minority Communities of Quebec - Quebec Community Groups Network (QCGN) (2002)
The following discussion paper is a resource document created for the Global Development Plan (GDP) Working Group, which is based on highlights of various readings. The intention of this document is to generate discussion concerning the Quebec English-speaking community in terms of: How has the community evolved? Where are we now? Who are we?

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2001)

Annual Report 2000-2001 - Alliance Quebec (AQ) (2001)

Annual Report : 2000 - 2001 - NDG Community Council (NDGCC) (2001)

The Twentieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2001)

Africana Congress 2000 - Africana Studies Committee (2000)
Africana Congress 2000 was held at McGill University from February 4" to February 6” 2000. Organized by the Africana Studies Committee and the Black Student Network, and sponsored in large part by Canadian Heritage, the event served to celebrate and critically re-evaluate 30 years of Africana Studies at McGill University. The Congress marked a major turning point in the struggle to maintain and promote Africana Studies at McGill University. It was first conceived two years earlier, when the Africana Studies Committee (ASC) drafted its 1998 Development Plan, a document that charted ASC’s 20-year vision for the potential expansion of the program. The plan was divided into four phases, the final one being the establishment of an Africana Studies Centre. In the interim, the Congress was conceived and proposed as a way of mobilizing as much support for the initiative as possible. The Congress was also conceived as a forum that would welcome input and would generate discussion about how to achieve our goals. ASC without engaging in acknowledged that it could not achieve these ambitious, though not unrealistic, goals with genuine consultations with the wider community.

Alliance Quebec Elects New President - Alliance Quebec (AQ) (2000)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2000)

Alliance Quebec Identifies Priorities for the Coming Year - Alliance Quebec (AQ) (1999)

1999 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1999)

Alliance Quebec : A Needs Assessment Study - Alliance Quebec (AQ) (1999)
The pressures of resources - both human and financial – impose limits on studies of this scope that are unavoidable. Furthermore needs are very subjective in nature and may depend upon who identifies them, who evaluates them and where they are placed among other so-called needs. To assess the needs of any particular group as diverse as the community which Alliance Quebec serves is a daunting task. Alliance Quebec's unique provincial perspective clearly underscores that challenge facing all our communities, urban and rural, large and small, unilingual and multi-lingual. English-speaking Quebecers are increasingly ethnically diverse, ageing and in fear of the loss of our young to other parts of the country and the world. Obviously, given these circumstances, differences will surface as to what is a need and as to how the needs are to be determined. Even though we face common issues, there is nothing common about the way our communities face those issues.

Alliance Quebec is No Shell - Alliance Quebec (AQ) (1999)

Annual Report 1998-1999 - NDG Community Council (NDGCC) (1999)

1998 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1998)

1997 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1997)

AQ Re-elects Hamelin, Calls for Full Participation in Quebec Society - Alliance Quebec (AQ) (1997)

English-speaking Quebecers and the Federal Election - Alliance Quebec (AQ) (1997)

Mell to Challenge Hemelin for Alliance Quebec PResidency 21 Candidates to Run for AQ Board of Directors - Alliance Quebec (AQ) (1997)

The McGill Institute for Learning in Retirement (MILR) : By-laws - The McGill Institute for Learning in Retirement (MILR) (1996)

Michael Hamelin re-elected President of Quebec - Alliance Quebec (AQ) (1996)

1996 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1996)

AQ Fund-Raising Begins to Bear Fruit - Alliance Quebec (AQ) (1996)

Annual Report : 1995 -1996 - NDG Community Council (NDGCC) (1996)

1995 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1995)

Annual Report : 1994 -1995 - NDG Community Council (NDGCC) (1995)

1994 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1994)

Annual Report : 1993 -1994 - NDG Community Council (NDGCC) (1994)

1993 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1993)

English-Language Education in Québec : A Response to the Task Force on English Education - Advisory Board on English Education (1993)
It is the responsibility of the Minister of Education to ensure quality in the educational services provided by the education system to the population of Québec. It was with the objective of ensuring quality service to English-speaking students, that a task force on English education was mandated in September 1991 to examine four key areas of concern: the decline of the English school population, the situation of small schools, vocational education and the exodus of young English-speaking Quebecers. The English-speaking community has always been and continues to be an integral part of Québec society. It reflects the important diversity that has always been present in Québec, a diversity that offers strength and an outward-Iooking vision. English institutions not only give valuable service but also play an important role in developing leadership in the Québec community. These institutions deserve support and young anglophone Quebecers must feel that their schools are responsive and dynamic institutions which are changing with the times. English schools must provide these young people with, not only a knowledge of their past but also a vision of their future in Québec.

1992 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1992)

1991 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1991)

1990 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1990)

1989 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1989)

Annual Report : 1988 -1989 - NDG Community Council (NDGCC) (1989)

1988 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1988)

1987 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1987)

1986 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1986)

1985 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1985)

The Monthly Report - Alliance Quebec (AQ) (1984)

1984 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1984)

1983 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1983)

1982 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1982)

1981 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1981)

National Regional Committee National Congress of Black Women Report - Montreal Regional Committee National Congress of Black Women (1981)
The objectives of this Conference were aimed at sensitizing the general public (Black and White) i.e. parents and children, students and teachers, governmental and para-public organizations, to the racism and sexism found in the textbooks used in our school system, to develop solutions to these problems and to use our collective strength to bring about constructive social change.

1980 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1980)

1979 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1979)

Final Report on the Aspirations and Expectations of the Quebec Black Community with Regard to Education - The Black Community Work Group on Education (1978)

1978 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1978)

1977 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1977)

1976 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1976)

1975 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1975)

1974 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1974)

Programme de responsabilité sociale de l’entreprise / Corporate Social Responsibility Program - 4Korners

A Portrait of the Food Industry Relating To Residents of the Lower North Shore : A Healthy Alternative Lifestyle - Coasters Association

Board of Directors 2020-2021 - Coasters Association

Coasters Association Board of Directors : 2022-2024 - Coasters Association

Getting Ahead of Adversity : Coasters Association: Self Care Work Life Balance - Coasters Association

Northern Research Center : Social Development Framework - Coasters Association

CEDEC : Career Focus Project Ideas - Community Economic Development and Employability Corporation (CEDEC)

Grandma's Kitchen Table : Tips, Resources and Recipes - Council for Anglophone Magdalen Islanders (CAMI)

Partnering to Meet the Growing Needs of English-Speaking Seniors During the Pandemic - Council for Anglophone Magdalen Islanders (CAMI)

The Future is Now : Towards a Community Vision for the Future of the English-speaking Community of The Magdalen Islands - Council for Anglophone Magdalen Islanders (CAMI)

CEDFOB : Research Report & Projects - Evans, Callie (Coasters Association)

Social Development Framework for the Development of the Lower North Shore - Fequet, Shelley
The Lower North Shore has seen a lot of changes of the past ten years while ongoing challenges still persist, despite efforts made by multiple organizations. As a “Lower North Shore community”, we all try to get a grasp on the community and social influences of the current local and global changes, including advances in technology, environmental realities, outmigration, emerging economies and aging population.

Users and Residents : Have Your Say / Usagers et résidents : La parole est à vous - Jeffery Hale – Saint Brigid’s (JHSB) Users' Committee

Youth Engagement Guide & Toolkit - Kippen, Kayla; Etheridge, Honlee (Coasters Association)

5 Key Mobilization Strategies in Minoritiy Community Contexts - Kueber, Russ

From Involvement to Engagement - Leading English Education and Resource Network (LEARN)

Your Family Makes a Difference - Leading English Education and Resource Network (LEARN)

Family Literacy Toolkit : Resources, Planning Guide, Best Practices - Literacy Quebec (LQ)
Literacy Quebec is a network that connects and represents community-based literacy organizations to empower people, impact lives and build a stronger society. We envision a Quebec where everyone has the literacy skills they need to live a fully engaged life.

Map of Literacy Volunteers of Quebec Members - Literacy Volunteers of Quebec

Milestones in LVQ History - Literacy Volunteers of Quebec

Empowering a Community Through Education and Career Support - Phelps Helps

Community Development Plan for the English-speaking Communities of Quebec 2005-2010 - Quebec Community Groups Network (QCGN)
Profound social, economic and political changes have transformed Quebec society during the past forty years. As we enter the 21st century, we are far enough away from the most intense upheaval and emotional turbulence to look back with a measure of objectivity. As we plan for the future, it is opportune to reflect upon past conditions that brought us to where we are today. Our minority community feels vulnerable. Demographic trends are disturbing and seemingly irreversible. We often feel that the majority neither understand us nor will make any serious effort to defend us. We have to fight for our survival.

Proposed Logic Model for Community Development Plan - Quebec Community Groups Network (QCGN)

Quebec Community Groups Network Mission Statement - Quebec Community Groups Network (QCGN)

Quebec's English-speaking Community Development Plan - Quebec Community Groups Network (QCGN)

[What is the QCGN?] - Quebec Community Groups Network (QCGN)

Benefits of QWF Membership - Quebec Writers' Federation (QWF)

Membership Benefits - Regional Development Network (RDN)

Building a New Bridge of understanding and discovery of the English-speaking Community of the Monteregie Centre (South Shore) - Richardson, Mary (Assistance and Referral Centre)

The Genesis of a Black-Community Based Observatory - Rochat, Désirée

Memory Garden Project / Projet Jardin Souvenir - Saint Brigid’s Home

QCGN Fêtes 10th Anniversary of Community Awards - Vongdouangchanh, Bea

Jump Start Your Job Search : Readiness Questionnaire - Youth Employment Services (YES)

The 10th Annual YES Entrepreneurship Conference : YES, The Future is Yours : Workshops - Youth Employment Services (YES)

YES Conference Agenda - Youth Employment Services (YES)

YES E-News Monthly - Youth Employment Services (YES)

Recommendations to Address Community Disengagement Amongst Quebec's English-speaking Youth Population - Youth for Youth Québec (Y4Y Québec)